Method for manufacturing or recycling member for electrochemical device, method for manufacturing electrochemical device, member for electrochemical device, and electrochemical device

By using molding material compositions without organic solvents and extrusion operations, the problem of irreversible changes caused by solvent reduction or hygroscopy in the manufacturing of electrochemical devices is solved, and stable production and safe operation are achieved.

CN114830374BActive Publication Date: 2025-03-28ZEON CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202080086844.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-27
Filing Date
2020-12-25
Publication Date
2025-03-28
Estimated Expiration
2040-12-25

AI Technical Summary

Technical Problem

In the prior art, when manufacturing electrochemical devices, it is difficult to prevent irreversible changes caused by solvent reduction or hygroscopy, and the operator has a higher risk of exposure to volatile organic solvents.

Method used

The members for electrochemical device are prepared by extrusion operations such as extrusion, injection into the mold, stretching, etc. using molding material compositions that do not contain organic solvents, including fillers, plasticizers and polymers.

Benefits of technology

It effectively suppresses irreversible changes in the electrochemical device composition caused by solvent reduction or hygroscopy during the manufacturing process, improves production stability and device performance, and reduces the health risks of operators.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The object of the present invention is to provide a method for manufacturing a component for an electrochemical device, etc., which is not prone to irreversible changes in the composition of the electrochemical device due to solvent reduction, moisture absorption, etc. during the manufacture of the electrochemical device. The method for manufacturing a component for an electrochemical device of the present invention includes performing at least one shaping operation described in this specification on a molding material composition having plasticity and self-supporting properties, wherein the molding material composition comprises: at least one filler (F); a plasticizer (P-S) that is water, an ionic liquid, or a mixture thereof; and a polymer (P1), which does not substantially contain an organic solvent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing or recycling an electrochemical device member, a method for producing an electrochemical device, an electrochemical device member, and an electrochemical device. Background Art

[0002] Electrodes containing active materials have been used in primary batteries such as lithium primary batteries; non-aqueous secondary batteries such as lithium ion secondary batteries, lithium metal secondary batteries, sodium ion secondary batteries, potassium ion secondary batteries, magnesium secondary batteries, and aluminum secondary batteries; air batteries; solar cells such as dye-sensitized solar cells; capacitors such as double-layer capacitors and lithium ion capacitors; electrochromic display devices; electrochemiluminescent elements; double-layer transistors; and electrochemical actuators.

[0003] Moreover, for example, Patent Document 1 records that the technical problem to be solved is to provide an electrode paste in which the contact surface area between the active material particles and the solution is uniform, and also records a method for manufacturing the electrode paste, namely, using a chemically dried material, mixing the active material solid particle component with a liquid non-volatile plasticizer component and a volatile anhydrous pulverizing solvent to form a slurry, pulverizing the slurry until the particle size and particle size distribution reach the desired values, and removing the volatile anhydrous pulverizing solvent, thereby manufacturing the electrode paste.

[0004] In addition, for example, Patent Document 2 describes a method for manufacturing a positive electrode plate for a non-aqueous battery: a paste mainly composed of active material powder such as manganese dioxide, a binder composed of a fluororesin that is fiberized in an unsintered state to form a bonding network, and a solution of a viscous agent composed of polyethylene oxide is applied to the electrode core, and then heat treated at a temperature below the decomposition temperature of the above-mentioned polyethylene oxide to remove moisture.

[0005] Furthermore, for example, Patent Document 3 describes an electrolyte composition for an electrochemical device comprising an ionic substance and a plasticizer composed of an organic compound containing a high-boiling point organic compound, an electrode for an electrochemical device comprising an electrode composite material layer obtained by molding a mixture obtained by mixing the electrolyte composition for an electrochemical device and an electrode active material, and methods for manufacturing the same.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent document 1: Japanese Patent Application Publication No. 10-334886;

[0009] Patent document 2: Japanese Patent Application Publication No. 61-91861;

[0010] Patent document 3: Japanese Patent Application Publication No. 2019-114390. Summary of the invention

[0011] Problem that the invention aims to solve

[0012] The technology described in Patent Documents 1 and 3 is to apply a molding material (paste, slurry, mixture) obtained by mixing an active substance in an electrolyte to a current collector or to mold the material on the current collector, and to manufacture electrodes in a manner that the non-aqueous organic solvent in the electrolyte is not completely volatilized. However, in such a manufacturing method, there are the following problems: when the molding process is in an open environment, it is difficult to replenish the organic solvent of the volatile part when more than the necessary amount of non-aqueous organic solvent has volatilized. In addition, when moisture absorption occurs, it is difficult to remove the moisture absorbed, so once the quality changes, it is difficult to restore. In order to obtain stable production and stable device performance, the volatilization amount must be managed. In addition, in the process of manufacturing electrodes, if proper management is not performed, there is also a risk that the operator is exposed to the volatilized non-aqueous organic solvent, which is also a problem.

[0013] In addition, although the technology described in Patent Document 2 studies the applicability of the manufacture of positive electrodes for lithium primary batteries, it does not study the applicability of the manufacture of components for other batteries such as lithium-ion secondary batteries. In addition, the technology described in Patent Document 2 does not study the quality changes and quality recovery of components caused by changes in the amount of solvent in the manufacturing process. In particular, compared with primary batteries, the unit area weight accuracy of the electrodes of secondary batteries (such as the thickness of the electrodes, the accuracy of the surface roughness of the electrodes) is more important, but the technology described in Patent Document 2 does not study the unit area weight accuracy of the electrodes. In addition, there is no forming operation to form components.

[0014] Therefore, an object of the present invention is to provide a method for producing a member for an electrochemical device, which is less likely to cause irreversible changes in the composition of the electrochemical device due to solvent reduction, moisture absorption, etc. during the production of the electrochemical device.

[0015] Solutions for solving problems

[0016] The inventors of the present invention have conducted in-depth research to achieve the above-mentioned purpose, and as a result, have found that by subjecting the following molding material composition to a prescribed shaping operation, it is possible to manufacture components for electrochemical devices in which irreversible quality changes during the manufacturing process are suppressed, thereby completing the present invention. The above-mentioned molding material composition comprises a filler, a plasticizer which is water, an ionic liquid, or a mixture thereof, and a polymer, and does not substantially contain an organic solvent, has plasticity and self-supporting properties, and the polymer can be plasticized by the plasticizer.

[0017] That is, the object of the present invention is to advantageously solve the above-mentioned problems. The method for manufacturing a member for an electrochemical device of the present invention is characterized in that it comprises subjecting a molding material composition to at least one shaping operation selected from the following group A,

[0018] The molding material composition has plasticity and self-supporting properties, comprises at least one filler (F), a plasticizer (PS) which is water, an ionic liquid, or a mixture thereof, and a polymer (P1), and substantially does not contain an organic solvent.

[0019] [Group A: extrusion, injection into a mold, stretching, compression molding, reducing thickness by pressurization, making thickness uniform by pressurization, cutting, drilling, cutting, bending into a final shape to be housed in an electrochemical device container, and bonding molding material compositions of different compositions together].

[0020] When an electrochemical device (for example, an electrode) is manufactured using the electrochemical device member manufactured in this manner, it is possible to suppress irreversible changes in the composition of the electrochemical device due to solvent reduction, moisture absorption, etc. during the manufacture of the electrochemical device.

[0021] The polymer (P1) may be a polymer that can also be plasticized by the electrolyte solvent (ES). In addition, the polymer (P1) may be a deliquescent polymer. The polymer (P1) is preferably a polymer containing ethylene oxide (EO) as a monomer unit, a polymer Oxazoline polymers, poly-N-vinylacetamide polymers, or epichlorohydrin-organic amine condensates.

[0022] The filler (F) may contain an active substance (A). In addition, the filler (F) may contain an inorganic solid electrolyte. In addition, the filler (F) may contain a fibrous substance. In addition, the filler (F) may contain a solid lubricant.

[0023] The fibrous substance may have a fiber length of 10 μm or more. In addition, the fibrous substance may have a fiber length that is greater than the thickness of the electrochemical device member. In addition, the fibrous substance may have a fiber diameter of nanometer size.

[0024] The solid lubricant may be selected from the following Group B.

[0025] [Group B: graphite, graphene, boron nitride, polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), molybdenum sulfide, tungsten disulfide, mica, talc, graphite fluoride, melamine cyanurate, metal soap].

[0026] The filler (F) may be nano-sized, and the volume fraction of the filler (F) in the molding material composition may be 50 volume % or more.

[0027] The molding material composition may further contain a polymer (P2) that can be plasticized by the plasticizer (PS) but is insoluble in the electrolyte.

[0028] The method for manufacturing the electrochemical device component of the present invention may include irreversibly crosslinking the polymer (P1). The crosslinking method may be thermal crosslinking. In addition, the crosslinking method may be UV crosslinking. In addition, a crosslinking agent may be added to the molding material composition. In addition, a crosslinking agent may be added to the electrolyte. In addition, the polymer (P1) may be a self-crosslinking polymer.

[0029] The method for manufacturing the electrochemical device component of the present invention may include managing the weight per unit area by measuring the thickness of the component and providing feedback. In addition, the method for manufacturing the electrochemical device component of the present invention may include crushing a plurality of strands formed from a molding material composition to form a sheet. In addition, the method for manufacturing the electrochemical device component of the present invention may include obtaining the component by shaving off from a block of the molding material composition.

[0030] In addition, the method for manufacturing a component for an electrochemical device of the present invention may include the step of attaching a molding material composition to a substrate. The method for manufacturing a component for an electrochemical device of the present invention may include the step of attaching the molding material composition to a substrate after forming the molding material composition into a desired thickness. In addition, the method for manufacturing a component for an electrochemical device of the present invention may include the step of attaching the molding material composition to the surface and back of the substrate substantially simultaneously. In addition, the method for manufacturing a component for an electrochemical device of the present invention includes the step of attaching the molding material composition to the back side after attaching the molding material composition to the surface side of the substrate. The substrate may have a conductive coating on the surface in contact with the molding material composition. In addition, the substrate may contain a polymer as the main body. In the method for manufacturing a component for an electrochemical device of the present invention, after attaching the molding material composition to the substrate, the component may not be cut or perforated together with the substrate.

[0031] The component may be an electrode or an insulating layer.

[0032] At least one of the shaping operations selected from group A can be performed without the molding material composition contacting the current collecting foil. In addition, at least one of the shaping operations selected from group A can be performed without the molding material composition contacting the porous separator.

[0033] In the case where the plasticizer (PS) is water or a mixture of water and an ionic liquid, the method for manufacturing a component for an electrochemical device of the present invention may include a step of removing moisture by a drying operation to form a non-plasticized state after the molding material composition is formed into the final shape when the component is configured in the device. The drying operation can be performed by vacuum or heating. In addition, the drying operation can be performed in a state where the molding material composition is not in contact with the current collecting foil. In addition, the drying operation can be performed in a state where the molding material composition is not in contact with the porous diaphragm.

[0034] The method for manufacturing an electrochemical device component of the present invention may include a step of peeling the molding material composition that has been attached to the substrate from the substrate. In addition, the method for manufacturing an electrochemical device component of the present invention may include a step of restoring the plasticized state by adding water or humidifying again after the molding material composition or the molding material composition that has undergone a cross-linking operation becomes a non-plasticized state. In addition, the method for manufacturing an electrochemical device component of the present invention may include a step of using the scraps of the molding material composition produced in the process of shaping the molding material composition to manufacture the next component again.

[0035] In addition, the method for recycling the electrochemical device component of the present invention includes a step of peeling the molding material composition that has been attached to the substrate from the substrate in the above-mentioned method for manufacturing the electrochemical device component. In other embodiments, it includes a step of restoring the plasticized state by adding water or humidifying again after the molding material composition becomes a non-plasticized state in the above-mentioned method for manufacturing the electrochemical device component. Furthermore, in other embodiments, it includes a step of using the scraps of the molding material composition produced in the process of shaping the molding material composition in the above-mentioned method for manufacturing the electrochemical device component to manufacture the next component again.

[0036] The molding material composition used in the present invention can suppress irreversible changes in the composition of the electrochemical device due to solvent reduction, moisture absorption, etc. during the production of the electrochemical device, so the electrochemical device member can be reused without changing its quality.

[0037] The method for producing an electrochemical device of the present invention includes the step of obtaining a member by the above-mentioned production method or recycling method.

[0038] In the method for manufacturing an electrochemical device of the present invention, the polymer (P1) may be a polymer that can also be plasticized by the electrolyte solvent (ES). In addition, in the method for manufacturing an electrochemical device of the present invention, the molding material composition may also include a polymer (P2) that can be plasticized by a plasticizer (PS) but is insoluble in the electrolyte. In addition, in the method for manufacturing an electrochemical device of the present invention, a crosslinking agent may be added to the electrolyte.

[0039] The electrochemical device member of the present invention is obtained by the above-mentioned production method or recycling method. The electrochemical device member may be an electrode or an insulating layer.

[0040] The electrochemical device of the present invention includes the above-mentioned electrochemical device member.

[0041] The electrochemical device of the present invention may include an electrode obtained by the above-mentioned manufacturing method or recycling method and a counter electrode opposite to the electrode, and the counter electrode may include at least one selected from alkali metals, alkaline earth metals, metal aluminum and silver.

[0042] The electrochemical device of the present invention may be an aqueous electrochemical device in which the carrier ions are at least any one of alkali metal ions, alkaline earth metal ions, aluminum ions, silver ions, organic nitrogen cations, and halide anions, bis(fluoromethanesulfonyl)imide bis(trifluoromethanesulfonyl)imide anions, and trifluoromethanesulfonic acid anions. As aqueous electrochemical devices, for example, electrochemical devices containing water in the electrolyte (for example, aqueous lithium ion secondary batteries, manganese zinc primary batteries, and other aqueous batteries) can be cited.

[0043] The electrochemical device of the present invention can be a non-aqueous electrochemical device. In addition, the electrochemical device of the present invention can be a non-aqueous electrochemical device in which the carrier ions are at least any one of alkali metal ions, alkaline earth metal ions, aluminum ions, silver ions, organic nitrogen cations, and halide anions, bis(fluoromethanesulfonyl)imide bis(trifluoromethanesulfonyl)imide anions, and trifluoromethanesulfonic acid anions. As a non-aqueous electrochemical device, for example, an electrochemical device that does not contain water in which the electrolyte is dissolved in an organic solvent (for example, non-aqueous batteries such as non-aqueous lithium ion secondary batteries, lithium primary batteries, and manganese lithium primary batteries) can be cited.

[0044] Effects of the Invention

[0045] According to the present invention, a method for producing and recycling an electrochemical device member can be provided, which is less likely to cause a problem of irreversible changes in the composition of the electrochemical device due to solvent reduction, moisture absorption, etc. during the production of the electrochemical device.

[0046] Furthermore, according to the present invention, it is possible to provide an electrochemical device member that is less likely to cause irreversible changes in the composition of the electrochemical device due to solvent reduction, moisture absorption, etc. during the manufacture of the electrochemical device, and an electrochemical device using the electrochemical device member. DETAILED DESCRIPTION

[0047] The manufacturing method and recycling method of the components for electrochemical devices of the present invention are not particularly limited, and can be used in the manufacture or recycling of components for, for example, the following electrochemical devices: non-aqueous or aqueous primary batteries such as lithium primary batteries, manganese primary batteries (e.g., manganese-zinc primary batteries, manganese-lithium primary batteries); non-aqueous or aqueous secondary batteries such as lithium-ion secondary batteries (non-aqueous, aqueous), lithium metal secondary batteries, sodium-ion secondary batteries, potassium-ion secondary batteries, magnesium secondary batteries, aluminum secondary batteries; air batteries; solar cells such as dye-sensitized solar cells; capacitors such as double-layer capacitors and lithium-ion capacitors; electrochromic display devices; electrochemiluminescent elements; double-layer transistors; electrochemical actuators, etc.

[0048] Furthermore, the electrochemical device member of the present invention can be produced or reused by the method for producing or reusing the electrochemical device member of the present invention.

[0049] Furthermore, the electrochemical device of the present invention can use the electrochemical device member of the present invention.

[0050] Furthermore, the electrochemical device is preferably a non-aqueous secondary battery, and more preferably a lithium ion secondary battery.

[0051] (Method for manufacturing member for electrochemical device)

[0052] The method for producing a member for an electrochemical device of the present invention comprises the step of subjecting a molding material composition to at least one shaping operation selected from the following group A,

[0053] The molding material composition is plastic and self-supporting, and comprises at least one filler (F), a plasticizer (PS) which is water, an ionic liquid or a mixture thereof, and a polymer (P1), and substantially contains no organic solvent. Preferably, the polymer (P1) can be plasticized by the plasticizer (PS).

[0054] [Group A: extrusion, injection into a mold, stretching, compression molding, reducing thickness by pressurization, making thickness uniform by pressurization, cutting, drilling, cutting, bending into a final shape to be housed in an electrochemical device container, and bonding molding material compositions of different compositions together].

[0055] <Molding material composition>

[0056] "Molding material composition" refers to a semi-solid material for forming a member for an electrochemical device. The molding material composition can be obtained by mixing at least one of the above-mentioned filler (F), plasticizer (PS) and polymer (P1), and any additional components under the condition of substantially not containing an organic solvent. These components can be mixed simultaneously or sequentially, and the order of adding the components constituting the molding material composition is not limited. The mixing operation can use an intermittent mixer, a continuous mixer, or both. The polymer can be added as a powder or as a solution dissolved in a solvent. From the viewpoint of uniform dispersion, it is preferred to mix the powdered materials with each other first. The mixing operation is not particularly limited, and can be carried out using known mixing devices such as a multi-axis extruder, a bead mill, a roll mixer, a closed mixer (for example, a kneader, a Banbury mixer, a planetary mixer, etc.), a high-speed stirring mixer (for example, a Henschel mixer, a coffee mill, etc.), a rotary granulator, and a fluidized bed granulator. The mixing operation temperature is preferably below the melting point of the polymer (P1), usually preferably below room temperature (35°C or below). The mixing operation temperature is preferably above the solidification point of the plasticizer (PS), usually preferably above 0°C. When the molding material composition is a powder, the risk of its fine powder entering the inside of an electrochemical device (e.g., a battery) or the inside of a manufacturing device increases, so the molding material composition of the present invention is handled in a clay-like (mixture-like) form.

[0057] The molding material composition used in the present invention has plasticity and self-supporting properties. In this specification, the molding material composition "has plasticity" means that under the condition of 25°C, a piece of molding material composition can be combined into one piece after being divided into two or more parts. In this specification, "having self-supporting properties" means that it has resistance to deformation and collapse due to its own weight when it is stationary and when moving in space, and can maintain its shape, that is, it means that the material can maintain its shape when it is stationary for a long time without being affected by its own weight, and can move in the air while maintaining its shape. Specifically, "having self-supporting properties" means: under the condition of 25°C, the shape can be adjusted to at least 10×10×2mm, the sheet does not flow when it is placed on a flat table, the shape does not change for at least 1 hour, and it is measured with 1 / 10cm 2 The sheet can be lifted by gripping it from the end of the sheet with tweezers of the following area. It can be said that the larger the area and the thinner the thickness, the higher the self-supporting property.

[0058] <Filler (F)>

[0059] Filler (F) refers to a solid substance that forms a component for an electrochemical device. Filler (F) is usually granular or powdery. Filler (F) may preferably be a solid substance having at least a short diameter smaller than the thickness of the component. As filler (F), for example, active material (A), inorganic solid electrolyte, fibrous material, solid lubricant, conductive material (for example, conductive carbon), reinforcing material, output enhancer, flame retardant, gas generator, plastic particles for increasing resistance, and other simple fillers without special functions can be cited. These classifications of fillers (F) are based on functions, uses, physical properties, etc., and the same substance can repeatedly belong to multiple classifications.

[0060] In the case where the filler is granular, when the particle size is reduced, the specific surface area increases and the cohesive force becomes stronger, so it is preferred. As filler (F), it is particularly preferred to use a filler of nanometer size (maximum diameter is less than 1 μm), and it is more preferred to use a filler with a volume average particle size of more than 100nm and less than 900nm. If a nanometer-sized filler is used, the contact interface area with the electrolyte becomes larger, so a component (for example, an electrode) with excellent strength can be formed, and a component (for example, an electrode) that can perform electrochemical reactions well can be formed. The diameter of the filler is preferably smaller than the thickness of the component itself, but even in the case where the aspect ratio is larger than the thickness of the component itself, if the minor diameter is smaller than the thickness of the component, it can be oriented laterally, so it can also be used.

[0061] In the present invention, the volume average particle size of the particulate filler can be measured in accordance with JIS K8825.

[0062] Moreover, the content of the filler (F) in the molding material composition is preferably 50% by volume or more, more preferably 60% by volume or more. If the content of the filler (F) is above the above lower limit, a component (e.g., electrode) that can be used to manufacture an electrochemical device with high functionality (e.g., high capacity) can be formed.

[0063] In the case where the cross-linking of the molding material composition is not performed, the one with a higher content of solid components in the component (e.g., electrode, separator) has higher self-supporting properties, so it is preferred. The content of solid components in the molding material composition is preferably 40vol% or more, 50vol% or more, 60vol% or more, or 70vol% or more. When the content of solid components in the molding material composition is greater than 80vol%, plasticity deteriorates, so it is preferably 80vol% or less. In the case where the device is a storage element, from the viewpoint of energy density, one with a higher active material density is preferred.

[0064] <Active substance (A)>

[0065] The active material (A) is not particularly limited, and any active material corresponding to the type of electrochemical device can be used. The active material (A) contained in the molding material composition may be composed of only one active material or a mixture of two or more active materials.

[0066] Examples of the active material (A) include electrode active materials (when the electrochemical device member is an electrode).

[0067] <Electrode active material>

[0068] In the case where the electrochemical device component is an electrode, the electrode contains an electrode active material as an active material (A). As an electrode active material, an electrode active material corresponding to the type of electrochemical device using the manufactured electrode can be used. As an example, when the electrochemical device is a battery (for example, a non-aqueous or aqueous secondary battery such as a lithium ion secondary battery (non-aqueous, aqueous), a lithium primary battery, a manganese primary battery (manganese-zinc primary battery, manganese-lithium primary battery) and other non-aqueous or aqueous primary batteries), as an electrode active material, there is no particular limitation, and the following electrode active materials can be used.

[0069] <Positive electrode active material>

[0070] As a positive electrode active material that can be used in a positive electrode composite material layer of a positive electrode of a battery (for example, a non-aqueous or aqueous secondary battery such as a lithium ion secondary battery (non-aqueous, aqueous), a lithium primary battery, a non-aqueous or aqueous primary battery such as a manganese primary battery (manganese-zinc primary battery, manganese-lithium primary battery), etc.), it is possible to use, for example, a transition metal-containing compound such as a transition metal oxide, a transition metal sulfide, a composite metal oxide of lithium and a transition metal, or elemental sulfur, a redox-active organic compound, etc. In addition, as a transition metal, for example, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, etc. can be cited.

[0071] Specifically, the positive electrode active material is not particularly limited, and includes: lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), lithium nickel oxide (LiNiO2), Co-Ni-Mn lithium-containing composite oxides, Ni-Mn-Al lithium-containing composite oxides, Ni-Co-Al lithium-containing composite oxides, olivine lithium iron phosphate (LiFePO4), olivine lithium manganese phosphate (LiMnPO4), Li 1+x Mn 2-x O4 (0<X<2) represented by lithium-excess spinel compounds, Li[Ni 0.17 Li 0.2 Co 0.07 Mn 0.56 ]O2、LiNi0.5 Mn 1.5 O4, MOF (Metal-Organic-Framework), benzoquinone, manganese dioxide, etc.

[0072] The above-mentioned positive electrode active materials may be used alone or in combination of two or more.

[0073] <Negative electrode active material>

[0074] The negative electrode active material of the negative electrode composite material layer that can be used in the negative electrode of a battery (for example, non-aqueous or aqueous secondary batteries such as lithium-ion secondary batteries (non-aqueous, aqueous), lithium primary batteries, non-aqueous or aqueous primary batteries such as manganese primary batteries (manganese-zinc primary batteries, manganese-lithium primary batteries)), for example, carbon-based negative electrode active materials, metal-based negative electrode active materials, and negative electrode active materials obtained by combining them.

[0075] Here, the carbon-based negative electrode active material refers to an active material that can be inserted (also referred to as "doped") with lithium and has carbon as the main skeleton. In addition, as the carbon-based negative electrode active material, specifically, carbonaceous materials such as coke, mesocarbon microbeads (MCMB), mesophase pitch-based carbon fibers, pyrolysis vapor-grown carbon fibers, phenolic resin sintered bodies, polyacrylonitrile-based carbon fibers, quasi-isotropic carbon, furfuryl alcohol resin sintered bodies (PFA) and hard carbon; and graphite materials such as natural graphite and artificial graphite can be cited.

[0076] In addition, the metal-based negative electrode active material refers to an active material containing a metal, generally referring to an active material containing an element capable of inserting lithium in the structure, and having a theoretical capacity of 500 mAh / g or more per unit mass when lithium is inserted. Moreover, as metal-based active materials, for example, lithium metal, single metals capable of forming lithium alloys (for example, Ag, Al, Ba, Bi, Cu, Ga, Ge, In, Mg, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, Ti, etc.) and their oxides, sulfides, nitrides, silicides, carbides, phosphides, oxalates, formates, etc. can be cited. Furthermore, oxides such as lithium titanate can be cited.

[0077] The above-mentioned negative electrode active materials may be used alone or in combination of two or more.

[0078] <Filling agent for insulating layer>

[0079] In the case where the component for the electrochemical device is an insulating component (such as a separator), the insulating component may include a filler for the insulating layer. As a filler for the insulating layer, a filler for the insulating layer corresponding to the type of electrochemical device using the manufactured insulating layer can be used. As a filler for the insulating layer, it can be arbitrarily selected from substances other than substances with conductivity (conductive materials), for example, one or more of a combination can be selected from simple fillers, solid electrolytes, fibrous substances, solid lubricants, reinforcing materials, output enhancers, flame retardants, gas generators, plastics that increase resistance, etc. It is better to include at least one substance with high heat resistance. Even if a conductive material is added, it is also possible if it is an amount that does not show conductivity as an insulating layer. As an example, in the case where the electrochemical device is a lithium ion secondary battery, as a filler for the insulating layer, as long as it is not a conductive material, it is not particularly limited, and particles composed of inorganic materials (i.e., non-conductive inorganic particles) and particles composed of organic materials (i.e., non-conductive organic particles) that are stably present and electrochemically stable in the use environment of the electrochemical device can be cited. Non-conductive inorganic particles are particularly preferred. Preferred examples of the non-conductive inorganic particles include those other than a substance having conductivity (conductive material) among simple fillers.

[0080] <Solid electrolyte>

[0081] From the viewpoint of improving ion conductivity, the molding material composition may contain an inorganic solid electrolyte as a filler (F). The inorganic solid electrolyte may be, for example, an ion conductive ceramic. Examples of the inorganic solid electrolyte include, for example, a Li-Ge-PS system conductor (e.g., Li 10 GeP2S 12 ), Li-Si-PS-Cl based conductors (e.g., Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 10.3 ), Li-La-Zr-O based conductors (e.g., Li7La3Zr2O 12 ) (the above are lithium ion conductors), β-alumina (sodium ion conductors), Rb-Cu-IC conductors (for example, RbCu4I 1.75 C 13.25 ) and other copper ion conductors, Ag-IWO based conductors (e.g., Ag6I4WO4) and other silver ion conductors, etc.

[0082] <Fibrous substances>

[0083] When a fibrous substance is added, it bridges between fillers such as inorganic particles to help the molding material composition aggregate, thereby achieving the effect of improving the strength of components (such as electrodes) for electrochemical devices. From the above viewpoint, the molding material composition can also contain a fibrous substance as a filler (F). As a fibrous substance, it is preferred that the fiber diameter at least has a fiber thickness below the thickness of the component and an aspect ratio of 100 or more. As a fibrous substance, fibers such as carbon, metal, plastic, natural polymer, and ceramic can be cited. Among them, nanofibers with a fiber diameter of less than 1 μm are preferred, preferably nanometer size (maximum diameter less than 1 μm). As nanofibers with such a fiber diameter, for example, carbon nanotubes (CNT), carbon nanofibers, cellulose nanofibers, polytetrafluoroethylene (PTFE), and ceramic nanofibers can be cited. The fiber length of the fibrous substance is not particularly limited. From the viewpoint of joining the fillers to each other, it can be, for example, more than 10 μm, preferably more than 20 μm, and more preferably more than 50 μm. From the viewpoint of the handleability of the raw materials, it can be, for example, less than 5 cm, preferably less than 1 cm, and more preferably less than 1 mm. Furthermore, from the viewpoint of orienting the fibers in the planar direction and thereby improving the tensile strength, the fiber length of the fibrous substance is preferably equal to or longer than the thickness of the electrochemical device member (eg, electrode).

[0084] When adding too much fibrous material, electrode density decreases, so the amount of fibrous material can be preferably below 8 mass parts, more preferably below 5 mass parts, further preferably below 3 mass parts relative to the molding material composition as a whole. Although there is also the prior art that only PTFE is used as a binding agent to make electrodes, a large amount of PTFE is needed more than 10 weight parts, and the density of the electrode is also easily decreased. In the present invention, the power of the fillers such as active material and conductive particles cohesive to each other is based on the adhesiveness of the polymer plasticized, so fibrous material plays an auxiliary role, does not need a large amount of addition.

[0085] <Solid lubricant>

[0086] From the viewpoint of smoothly performing molding and processing the molding material composition with less force, the molding material composition may contain a solid lubricant as a filler (F). Examples of the solid lubricant include the solid lubricants listed in the following B group.

[0087] [Group B: graphite, graphene, boron nitride, polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), molybdenum sulfide, tungsten disulfide, mica, talc, graphite fluoride, melamine cyanurate, metal soap].

[0088] Examples of the metal soap include magnesium stearate, magnesium laurate, magnesium palmitate, calcium stearate, calcium oleate, calcium laurate, calcium 12-hydroxystearate, calcium montanate, barium stearate, barium oleate, barium laurate, barium arachidate, barium behenate, zinc stearate, zinc oleate, zinc laurate, and lithium stearate.

[0089] The concentration of the solid lubricant relative to the molding material composition is not particularly limited. From the viewpoint of exhibiting lubricity, it can be, for example, 0.5% by weight or more, preferably 1% by weight or more, and more preferably 2% by weight or more. From the viewpoint of increasing the ratio of the active material and the insulating layer filler, it can be, for example, 5% by weight or less, preferably 8% by weight or less, and more preferably 10% by weight or less.

[0090] <Conductive materials>

[0091] From the viewpoint of improving the conductivity of the electrode, the molding material composition may include a conductive material as a filler (F). As the conductive material, for example, conductive carbon (for example, graphite, expanded graphite, graphene, acetylene black, Ketjen black (registered trademark), carbon nanohorns, fullerenes, CNT), metal powders (for example, aluminum, zinc, iron, copper, silver, gold, nickel, titanium) can be cited. The concentration of the conductive material relative to the molding material composition is not particularly limited. From the viewpoint of showing conductivity, it can be, for example, 1% by weight or more, preferably 3% by weight or more, more preferably 5% by weight or more, and from the viewpoint of increasing the ratio of the active material, it can be, for example, 25% by weight or less, preferably 20% by weight or less, more preferably 15% by weight or less.

[0092] <Reinforcement materials>

[0093] From the viewpoint of imparting reinforcement to the electrochemical device, the molding material composition may contain a reinforcing material as the filler (F). Examples of the reinforcing material include whiskers having a large aspect ratio.

[0094] <Output Enhancer>

[0095] From the viewpoint of improving the output of the electrochemical device, the molding material composition may contain an output enhancer as a filler (F). As an output enhancer, for example, a filler that assists ion dissociation and a filler that imparts output to the electrochemical device may be cited. As a filler that assists ion dissociation, for example, a nanofiller (for example, silicon dioxide, aluminum oxide, zirconium oxide, titanium dioxide) may be cited. In addition, as a filler that imparts output to the electrochemical device, for example, a ferroelectric such as barium titanate may be cited.

[0096] <Flame retardant>

[0097] From the viewpoint of improving the safety of the electrochemical device, the molding material composition may contain a flame retardant as a filler (F). As the flame retardant, for example, red phosphorus, aluminum hydroxide, magnesium hydroxide, antimony (for example, antimony trioxide), hypophosphite (Hypophosphite Acid) metal salts, cyclophosphazene oligomers, polyphosphazenes, aliphatic phosphoric acid amides (for example, DAIGUARD-850: Daihachi Chemical Industry), chlorinated paraffin (for example, EMPARA70: Ajinomoto Fine-Techno Co., Inc.), melamine cyanurate. The concentration of the flame retardant relative to the molding material composition is not particularly limited. From the viewpoint of exhibiting flame retardancy, it can be, for example, 5% by weight or more, preferably 8% by weight or more, and more preferably 10% by weight or more. From the viewpoint of not hindering the operation of the electrochemical device, it can be, for example, 25% by weight or less, preferably 20% by weight or less, and more preferably 15% by weight or less.

[0098] <Gas generating agent>

[0099] From the viewpoint of providing an effect of increasing electrode resistance by generating gas when the electrochemical device generates abnormal heat, thereby improving safety, the molding material composition may contain a gas generator (having the effect of generating gas and increasing electrode resistance when abnormal heat is generated) as a filler (F). Examples of the gas generator include melamine, melamine cyanurate, ammonium carbonate, ammonium chloride, sodium bicarbonate, and OBSH.

[0100] <Plastic particles that increase electrical resistance>

[0101] The molding material composition may contain plastic particles that increase resistance as filler (F) from the viewpoint of improving safety by melting when the electrochemical device generates abnormal heat to increase electrode resistance. Examples of the plastic particles that increase resistance include polyethylene and polypropylene.

[0102] <Simple filler>

[0103] The molding material composition may contain other simple fillers without special functions as fillers (F). Among simple fillers, fillers composed of non-conductive substances can also be used as fillers for insulating layers. Fillers that can be used as both simple fillers and fillers for insulating layers include, for example: inorganic oxide particles such as alumina (alumina, Al2O3), alumina hydrates (boehmite, AlOOH), gibbsite (Al(OH)3), silicon oxide, magnesium oxide (magnesia), magnesium hydroxide, calcium oxide, titanium oxide (titania), barium titanate (BaTiO3), ZrO, silicon dioxide, and alumina-silicon dioxide composite oxides; nitride particles such as aluminum nitride and boron nitride; covalent bond crystal particles such as silicon and diamond; insoluble ionic crystal particles such as barium sulfate, calcium fluoride, and barium fluoride; clay particles such as talc and montmorillonite, etc. Among them, from the viewpoint of improving heat resistance, as simple fillers, preferred are particles composed of aluminum oxide (aluminum oxide particles), particles composed of boehmite (boehmite particles), particles composed of titanium oxide (titanium oxide particles), and particles composed of barium sulfate (barium sulfate particles), more preferred are aluminum oxide particles, boehmite particles, and barium sulfate particles, and further preferred are aluminum oxide particles and barium sulfate particles.

[0104] Furthermore, these particles may be subjected to element substitution, surface treatment, solid solution formation, etc. as necessary. Furthermore, these particles may be used alone or in combination of two or more.

[0105] <Selection of filler (F)>

[0106] As a filler (F), it is possible to select a filler that is expected to contribute to the improvement of production efficiency or safety when manufacturing components for electrochemical devices, the improvement of performance or safety of components for electrochemical devices, and the stabilization of quality. As a filler that is expected to improve ion conductivity, for example, the above-mentioned inorganic solid electrolyte can be selected. In addition, as a filler that imparts reinforcement to the electrochemical device, the above-mentioned reinforcing material can be selected. In addition, as a filler that imparts flame retardancy to the electrochemical device, for example, the above-mentioned flame retardant can be selected. In addition, as a filler that increases the output of the electrochemical device, for example, the above-mentioned output enhancer (for example, a filler that assists ion dissociation, a filler that imparts output to the electrochemical device) can be selected. In addition, as a filler that imparts the effect of generating gas to increase electrode resistance when the electrochemical device is abnormally heated, for example, the above-mentioned gas generator can be selected. In addition, as a filler that has the effect of melting when the electrochemical device is abnormally heated and increasing the electrode resistance, for example, the above-mentioned plastic particles can be selected. In addition, as a filler that improves the conductivity of the electrode, for example, the above-mentioned conductive material can be selected. In addition, as a filler that has the effect of making the molding process go smoothly and being able to process the molding material composition with less force, for example, the above-mentioned solid lubricant can be selected.

[0107] <Additional ingredients>

[0108] The molding material composition used in the present invention may also include a second polymer (P2) that can be plasticized by a plasticizer (PS) but is insoluble in the electrolyte. In addition, the molding material composition used in the present invention may also include other additional components. As additional components, for example, a crosslinking agent may be mentioned.

[0109] <Polymer>

[0110] The "polymer" (polymer (P1), polymer (P2)) contained in the molding material composition refers to a molecule with a weight average molecular weight of 10,000 or more. Examples of the main chain of the polymer used in the present invention include, for example, an aromatic ring, a sugar chain, a peptide chain, a carbonate chain, a methylene chain, a polyether chain, a chain containing nitrogen in the main chain, or a composite thereof. In order to manufacture a flexible component for an electrochemical device, from the viewpoint of imparting flexibility to the molding material composition, the main chain of the polymer used in the present invention is preferably a non-cellulosic sugar chain, a peptide chain, a methylene chain, a polyether chain, or a polyethyleneimine chain, and most preferably a methylene chain, a polyether chain, or a chain containing nitrogen in the main chain. Examples of substituents or side chains bonded to the main chain of the polymer used in the present invention include, for example, a cyano group, a hydroxyl group, a carboxylic acid, a carboxylate, a chain ester, a cyclic ester, a chain amide, a cyclic amide, a pyridine group, A polymer may have a plurality of substituents or side chains, such as oxazoline, polyether chain, amine, ammonium, organic ammonium, etc. From the viewpoint of adjusting the solubility in a plasticizer or an electrolyte, the substituent or side chain of the polymer used in the present invention may be appropriately selected. For example, if the number of polar groups is increased, it becomes water-soluble, and if the number of polar groups is reduced, it becomes water-insoluble. In addition, the design may be made with reference to the SP value.

[0111] From the viewpoint of imparting viscosity to the polymer solution, the weight average molecular weight is preferably a higher one, preferably 50,000 or more, more preferably 100,000 or more. On the other hand, when there are many components with too high molecular weight, the surface of the molded product may be rough or the molding speed may be reduced, so it is preferred that the components greater than 10 million are less than 5% by weight of the total polymer solution, and it is more preferred that the components greater than 5 million are less than 5% by weight of the total polymer solution.

[0112] Specific examples of the polymer (polymer (P1), polymer (P2)) include polyethylene oxide, sodium polyacrylate, lithium polyacrylate, polyacrylate, polyvinyl alcohol, poly-N-vinyl pyrrolidone, polyvinyl acetate, Synthetic polymers such as oxazoline, polyacrylamide, poly-N-vinylacetamide, and copolymers containing these monomer units, and deliquescent polymers such as epichlorohydrin-organic amine condensation products (e.g., dimethylamine-epichlorohydrin-ethylenediamine copolymers, polyamidoamine epichlorohydrin), dextrin, cyclodextrins (α-cyclodextrin, β-cyclodextrin, or γ-cyclodextrin, etc.), tamarind gum, gum arabic, guar gum, carrageenan, quince seeds, pregelatinized starch, tragacanth gum, carob gum (Carob Gum), pectin, galactan, karaya gum, agar, algin, xanthan gum, dextran, succinoglycan, pullulan, collagen, gelatin, casein, alginate albumin, glucomannan, mucin, fucoidan, sulfated fucose, polyglutamic acid (γ-polyglutamic acid), mannan, mannose and other natural polymers, carboxymethyl starch, methyl hydroxypropyl starch, methyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, methyl hydroxypropyl cellulose, sodium cellulose sulfate, sodium carboxymethyl cellulose (CMC-Na), sodium alginate, propylene glycol alginate and other semi-synthetic polymers, but not limited to these. From the viewpoint of being able to maintain a plasticized state under a wide range of conditions, the polymer used in the present invention is preferably: a polymer containing ethylene oxide (EO) as a monomer unit (for example, polyethylene oxide, an ethylene oxide copolymer with a high content of ethylene oxide, an ethylene oxide copolymer with a low content of ethylene oxide), a polyethylene oxide copolymer, ... Oxazoline polymers (e.g. Oxazoline, In some embodiments, the present invention can be used in the following embodiments: the present invention can be used in the following embodiments: poly-N-vinyl acetamide (e.g., poly-N-vinyl acetamide, N-vinyl acetamide copolymer), poly-N-vinyl pyrrolidone, polyvinyl acetate, and epichlorohydrin-organic amine condensation product (e.g., dimethylamine-epichlorohydrin-ethylenediamine copolymer, polyamide amine epichlorohydrin). "Content rate is high" in this specification refers to that the ratio of monomer units in all monomer units in the copolymer is, for example, more than 50mol%, preferably more than 60mol%, more than 70mol%, more than 80mol% or more than 90mol%. "Content rate is low" in this specification refers to that the ratio of monomer units in all monomer units in the copolymer is, for example, less than 50mol%, preferably less than 40mol%, less than 30mol%, less than 20mol% or less than 10mol%. When the molding material is alkaline, the polymer used in the present invention is preferably a polymer of poly-N-vinyl acetamide, poly-N-vinyl pyrrolidone, polyacrylic acid or alginic acid. From the viewpoint that water is not easily lost during molding, the polymer used in the present invention is preferably a deliquescent polymer such as epichlorohydrin-dimethylamine polycondensate (e.g., dimethylamine-epichlorohydrin-ethylenediamine copolymer). From the viewpoint of well maintaining the filler in the component, the viscosity of the polymer used in the present invention is preferably a viscosity that can achieve high viscosity, and the viscosity of the polymer solution is, for example, 100 cP or more, preferably 500 cP or more, more preferably 1000 cP or more, and preferably 5000 cP or more. The polymer used in the present invention is preferably a non-gelled polymer. The viscosity of the polymer solution can be measured by the following method.

[0113] In the present invention, "viscosity" refers to the viscosity measured at 25°C using an EMS viscometer (EMS-1000S manufactured by Kyoto Electronics Industries) at 1000 rpm under closed conditions so that the composition of the polymer solution does not change and moisture in the air does not mix in. The viscosity measured by this measurement method is basically the same value as the value measured in accordance with JIS Z8803.

[0114] From the viewpoint of the flexibility of components for electrochemical devices (such as electrodes), the amount of polymer in the polymer solution is preferably less than 90wt%, and in order to show moldability, it needs to be more than 1wt%, preferably more than 3wt%. In order to meet the condition of "polymer" in the molding material composition, it is necessary to be a "polymer" during the molding process, and does not include substances that are polymerized in electrochemical devices (such as batteries) to become polymers. When the polymer cannot be plasticized by the electrolyte solvent, the flexibility of the electrode is low, and it is possible to cause damage due to deformation caused by external forces and deformation caused by chemical reactions accompanying the operation of the device. If the component contains a polymer that is soluble in the electrolyte solvent, the flexibility of the electrode can be maintained, and even if the device is deformed, the possibility of damage is low.

[0115] <First polymer (P1)>

[0116] In the method for manufacturing a component for an electrochemical device of the present invention, the first polymer (P1) can be plasticized by a plasticizer (PS), so as a polymer (P1), a polymer having the property of being plasticized by a plasticizer (PS) used in the present invention can be used. In addition, from the viewpoint of maintaining flexibility after the electrochemical device is made, the polymer (P1) preferably has a polymer having the property of being plasticized by an electrolyte solvent (ES). In addition, in the case where the method for manufacturing a component for an electrochemical device of the present invention includes crosslinking the polymer (P1), the polymer (P1) can be a crosslinking polymer. As a crosslinking polymer, for example, an irreversible crosslinking polymer and a reversible crosslinking polymer can be cited, preferably an irreversible crosslinking polymer. In addition, as a crosslinking polymer, for example, a thermal crosslinking polymer and a UV crosslinking polymer can be cited. In addition, as a crosslinking polymer, for example, a polymer crosslinked with a crosslinking agent and a self-crosslinking polymer can be cited. As a polymer crosslinked with a crosslinking agent, a polymer having a crosslinking group such as an unsaturated bond, an epoxy group, and an oxetane group in the molecule can be cited. The polymer (P1) can be appropriately selected from the above-mentioned polymers according to the types of the plasticizer (PS) and the electrolyte solvent (ES). Examples of combinations of the polymer (P1), the plasticizer (PS) and the electrolyte solvent (ES) include those described below.

[0117] <Second polymer (P2)>

[0118] The molding material composition may also include a second polymer (P2) that can be plasticized by a plasticizer (PS) but is insoluble in the electrolyte. In this case, in the method for manufacturing a component for an electrochemical device of the present invention, the first polymer (P1) and the second polymer (P2) can be plasticized by a plasticizer (PS). The molding material composition includes a polymer (P2) which is beneficial for limiting the contact between the filler and the electrolyte. By limiting the contact between the filler and the electrolyte, useless reactions are suppressed and the life of the electrochemical device is prolonged. The polymer (P2) can be appropriately selected from the above-mentioned polymers according to the types of the plasticizer (PS) and the electrolyte. As examples of combinations of polymers (P2) with plasticizers (PS) and electrolytes, examples such as those described below can be cited.

[0119] <Plasticizer (PS)>

[0120] The plasticizer (PS) is water, an ionic liquid, or a mixture thereof. As ionic liquids, for example, N,N-diethyl-N-methyl-N-(2-methoxyethyl) ammonium bis(trifluoromethanesulfonyl)imide (DEME-TFSI, a water-insoluble ionic liquid), 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMI-TFSI, a water-insoluble ionic liquid), N,N-diethyl-N-methyl-N-(2-methoxyethyl)-tetrafluoroborate (DEME-BF4, a water-soluble ionic liquid), etc. can be cited, but are not limited thereto and can be widely selected from ionic liquids that can plasticize the polymer (P1) at 25°C. In addition, in the case where the electrochemical device has an unsealed part such as an actuator or an air battery, moisture in the air is also included in the electrolyte solvent (ES). In the case of processing with water and an ionic liquid, the ionic liquid will remain even if all the water has volatilized, so the battery component can maintain a certain degree of softness. When processed only with ionic liquids, the battery components are always soft. The amount of plasticizer (PS) used to plasticize the polymer is not particularly specified, and is mostly 5% by weight or more relative to the weight of the polymer. If it is 10% by weight or more, it can be plasticized in most cases. In addition, the content of plasticizer (PS) in the molding material composition can be, for example, 3% by weight or more, preferably 5% by weight or more. In short, it is better to confirm it by looking at the actual properties rather than the amount.

[0121] <Electrolyte solvent (ES) and electrolyte>

[0122] As electrolyte solvent (ES) and electrolyte, there are no particular limitations, and any electrolyte used in an electrochemical device can be used. As electrolyte solvent (ES), for example, organic solvents such as substances (water, ionic liquids, or mixtures thereof) that can be used as plasticizers (PS), propylene carbonate (PC), ethylene carbonate, chain carbonates, lactones, chain carboxylates, acetonitrile, sulfolane, glycol dimethyl ethers, chain sulfones, dinitrile compounds, cyclic ethers, and fluorinated ethers can be cited. Examples of the electrolyte include, for example, a solution in which an electrolyte (e.g., sodium chloride, potassium chloride, ammonium chloride, zinc chloride, lithium sulfate, magnesium sulfate, sulfuric acid, sodium hydroxide, lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium tetrafluoroborate (LiBF4), magnesium bis(trifluoromethanesulfonyl)imide (Mg(TFSI)2), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI)) is dissolved in an electrolyte solvent (ES) and an electrolyte solvent (ES) that can also serve as an electrolyte (e.g., an ionic liquid, a mixture of water and an ionic liquid). Examples of the ionic liquid include, for example, the above-mentioned ionic liquids. For devices having thick electrodes greater than 100 μm, it is preferred to select solvents or salts with high ion conductivity. Specifically, as a solvent, it is preferred to include any one of water, acetonitrile, ethylene glycol dimethyl ether, methyl acetate, bis(2,2,2-trifluoroethyl) ether, and 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether. As an electrolyte salt, it is preferred to include a salt of FSI anions.

[0123] <Examples of polymers (P1) and (P2)>

[0124] When the plasticizer (PS) is water and the electrolyte solvent (ES) is propylene carbonate (PC), examples of polymers that can be selected as the polymer (P1) include polyethylene oxide (PEO), EO copolymers with a high EO content, and polyethylene oxide (PEO). In this case, the polymer that can be selected as the polymer (P1) that can also be plasticized by the electrolyte solvent (ES) includes, for example, PEO, EO copolymers with a high content of EO, poly (PEO), and poly (EO). In this case, examples of polymers that can be selected as the polymer (P2) include CMC, sodium polyacrylate, sodium alginate, and PVOH.

[0125] When the plasticizer (PS) is water and the electrolyte solvent (ES) is water, the polymer that can be selected as the polymer (P1) includes, for example, PEO, EO copolymers with a high EO content, CMC, sodium polyacrylate, sodium alginate, PVOH, polyethyleneimine, poly In this case, a polymer (P1) that can also be plasticized by the electrolyte solvent (ES) can be selected from these polymers.

[0126] When the plasticizer (PS) is an ionic liquid and the electrolyte solvent (ES) is an ionic liquid, the polymer (P1) includes, for example, PEO, EO copolymers with a high EO content, EO copolymers with a low EO content, styrene acrylic copolymers, cellulose, and poly(ethylene glycol). In this case, a polymer (P1) that can also be plasticized by the electrolyte solvent (ES) can be selected from these polymers.

[0127] When the plasticizer (PS) is an ionic liquid and the electrolyte solvent (ES) is a mixed liquid of the ionic liquid and water, the polymer (P1) includes, for example, PEO, EO copolymers with a high EO content, and poly(ethylene glycol). In this case, the polymer that can be selected as the polymer (P1) that can also be plasticized by the electrolyte solvent (ES) includes, for example, PEO, EO copolymers with a high EO content, poly(vinyl acetamide), EO copolymers with a low EO content, styrene acrylic copolymers, and cellulose. In this case, examples of polymers that can be selected as the polymer (P2) include EO copolymers having a low EO content, styrene acrylic copolymers, and cellulose.

[0128] <Plasticized polymer>

[0129] The polymer is "plasticized" when it loses its fixed shape (liquid or rubbery) by mixing it with a solvent (e.g., plasticizer (PS), electrolyte solvent (ES), electrolyte), and a piece of plasticized polymer can be combined into one piece after being divided into two or more parts. However, since it is impossible to judge after the cross-linking operation, the properties in the uncross-linked state are also cited in the cross-linked body. In the case where the plasticizer (PS) is an ionic liquid with a repeating structure, the ionic liquid itself is regarded as the "polymer (P1) plasticized by the plasticizer (PS)".

[0130] The amount of the plasticizer (PS) used to plasticize the polymer (P1) is not particularly limited as long as it is an amount that can plasticize the polymer (P1). The amount of the plasticizer (PS) is usually 5% by weight or more relative to the polymer (P1), and if it is 10% by weight or more, it can be plasticized in most cases.

[0131] <Organic solvents>

[0132] The molding material composition used in the present invention does not substantially contain an organic solvent. "Organic solvent" refers to a non-ionic organic compound with a molecular weight of 1000 or less that is neither a polymer nor an ionic liquid. When an organic solvent is contained, it is not preferred from the perspective of fire and the health of the operator, but since a small amount of addition does not hinder the implementation of the present invention, it can be added to a total amount of 10% by weight or less relative to the total amount of the polymer and the plasticizer (PS) in the molding material composition.

[0133] <Pseudo cross-linking agent>

[0134] The molding material composition used in the present invention may further include the following components and structures (formation of pseudo crosslinks). When the molding material composition includes the following components and structures, pseudo crosslinks are formed, and the strength of the component can be increased without losing plasticity.

[0135] Polyvalent ions (especially polyethers and polyvalent cations, carboxylic acids and polyvalent cations, polyvinyl alcohol and polyvalent cations, polymers with cationic groups and polyvalent anions, polyethyleneimines and polyvalent ions);

[0136] Polyethyleneimine and polycarboxylic acid compounds;

[0137] Polyvinyl alcohol and borates / borax (sodium tetraborate, lithium tetraborate); or

[0138] A triblock polymer with both ends hydrophobized.

[0139] <Other components of molding material composition>

[0140] The molding material composition used in the present invention may further contain an acid, a base, or an electrolyte salt for operating the device.

[0141] <Composition ratio of components of molding material composition>

[0142] When it is desired to improve the self-supporting property of the molding material composition used in the present invention, the self-supporting property can be improved by adding a fiber component, increasing the amount of a filler, reducing the particle size of the filler, or increasing the amount of a polymer.

[0143] <Shaping operation>

[0144] The electrochemical device member of the present invention is produced by subjecting the above-mentioned molding material composition to at least one shaping operation selected from the following group A.

[0145] [Group A: extrusion, injection into a mold, stretching, compression molding, reducing thickness by pressurization, making thickness uniform by pressurization, cutting, drilling, cutting, bending into a final shape to be housed in an electrochemical device container, and bonding molding material compositions of different compositions together].

[0146] The molding material composition used in the present invention has plasticity and self-supporting properties, so it can be given a shape of the target electrochemical device component by a shaping operation, and the given shape can be maintained through the manufacturing process. In addition, since the desired shape can be given without drying and other operations, compared with the case where the slurry is applied and dried to form the device component, the quality change of the component caused by the change of the amount of solvent such as water in the manufacturing process can be suppressed, and the quality can be restored by absorbing solvents such as water after formation.

[0147] The excipient operation selected from group A can be performed in different types of operations, or the same operation can be repeated multiple times, and at least one of the excipient operations can be performed in a state where the molding material composition is not in contact with the collector foil. In addition, at least one of the excipient operations selected from group A can be performed in a state where the molding material composition is not in contact with the porous separator.

[0148] The shaping operation can be performed using known processing devices such as rollers, presses, cutters, milling cutters, and drills. The surface of the roller is preferably metal, ceramic, glass, fluorine-based polymer, or silicone-based polymer. The surface is preferably non-adhesive. The roller can also be provided with fine bumps to control adhesion. In the shaping operation, when the component is temporarily placed, it can be placed on a net, a porous plate, or a pickup fixture processed into a pleated or pear-skin shape. In the shaping operation, in order to control the thickness, a tape of a certain thickness can be pasted on the roller. When the roller is pre-patterned with a pattern, the component can be shaped by transferring its shape. When a roller is used to shape the component, a small-diameter roller is preferred because the amount of material attached is small and it is convenient to clean.

[0149] In the shaping operation, the molding material composition can be formed into a sheet. The thickness accuracy in the case of forming into a sheet is preferably within ±10%, and more preferably within ±5%. The close adhesion with the collector foil and other components is improved. When the sheet surface is corrugated, it is not easy to stick to the shaping device such as the roller, so it is preferred. In addition, it is easy to crush, so the thickness is easy to control. The operation of making the sheet surface corrugated can be made into a corrugated shape by pre-forming the mold outlet, or it can be formed by extruding it in a flat shape and then shaping it with a grooved roller or embossing roller, or cutting a groove with a knife. The height difference between the highest and lowest parts of the concave and convex is preferably more than 10% of the average thickness. The thicker one of the components has less adhesion to the device and is easy to manufacture. The thickness of the component is preferably more than 100μm. It can be more preferably more than 200μm. In the case where the component is an insulating layer, from the perspective of adhesion and followability to other components, the insulating layer is preferably thin. When the insulating layer is too thick, the insulating layer is easily peeled off at the interface. The thickness of the insulating layer may be preferably 100 μm or less, more preferably 50 μm or less, and further preferably 20 μm or less.

[0150] The molding material composition is preferably kept in a sealed container as much as possible when not in use. In addition, a protective film to prevent moisture absorption and drying can be pasted on the molding material composition during the process or storage.

[0151] <Additional Process>

[0152] The method for producing an electrochemical device member of the present invention may further include, for example, the following additional steps.

[0153] <Crosslinking of polymer (P1)>

[0154] The method for manufacturing a member for an electrochemical device of the present invention may further include a step of crosslinking the polymer (P1). As crosslinking, for example, irreversible crosslinking and reversible crosslinking can be cited, preferably irreversible crosslinking. In addition, as crosslinking, known crosslinking methods such as thermal crosslinking, UV crosslinking, electron beam crosslinking, and radiation crosslinking can be used. The crosslinking of electrodes and conductive layers is preferably thermal crosslinking and electron beam crosslinking. The crosslinking of the insulating layer is preferably UV crosslinking because the material is transparent. In addition, as crosslinking, for example, crosslinking and self-crosslinking using a crosslinking agent (such as a UV initiator) can be cited. In the case of crosslinking using a crosslinking agent, the crosslinking agent is preferably added to the electrochemical device, for example, it can be added to the molding material composition, and it can also be added to a part other than the molding material composition (such as an electrolyte). In addition, a low molecular weight co-crosslinking agent having multiple crosslinking groups such as TAIC (triallyl isocyanurate) can be used in combination. The polymer (P1) and the crosslinking agent can be appropriately selected according to the crosslinking method. For example, in the case where the crosslinking is self-crosslinking, the polymer (P1) can select a self-crosslinking polymer. To make a polymer into a self-crosslinking polymer, it is sufficient to make a polymer containing, for example, acetoacetyl, epoxy, oxetane, azetidinium, pyrrolidonyl, etc. Such a self-crosslinking polymer can be self-crosslinked by heating. The crosslinking of polymer (P1) can be carried out in any period of time during or after the plasticization of polymer (P1) with plasticizer (PS), or in any period of time before, during, or after the shaping operation. The crosslinking operation is preferably carried out in the plasticized state of polymer (P1), and can also be carried out before the device is assembled, or by the heating device itself after the device is assembled. In addition, in the manufacture of an electrochemical device, each component can be crosslinked and then assembled, but when the structure of the electrochemical device is completed and then crosslinked, the overall integration can be made to improve durability, so it is preferred.

[0155] <Feedback Management>

[0156] The manufacturing method of the electrochemical device component of the present invention may also include a feedback management process. As a feedback management process, for example, managing the unit area weight by measuring the characteristics of the component (such as thickness) and providing feedback can be cited. As a feedback management process, for example, the unit area weight can be measured by measuring the characteristics of the component (such as thickness). A manufacturing method that manages the unit area weight and provides feedback by measuring the thickness can be implemented. In such a feedback management process, it is not necessarily necessary to use X-rays or gamma rays to measure the unit area weight of the component, and a contact film thickness meter or a laser film thickness meter can be used for measurement.

[0157] <Molding related processes>

[0158] The method for manufacturing a component for an electrochemical device of the present invention may include a step of crushing a plurality of strands formed by a molding material composition to form a sheet. In addition, the method for manufacturing a component for an electrochemical device of the present invention may include a step of obtaining a component by shaving off a block of a molding material composition. In addition, the method for manufacturing a component for an electrochemical device of the present invention may include a step of attaching the molding material composition to a substrate (e.g., a current collector, a porous diaphragm). The attachment to the substrate may be performed, for example, after the molding material composition is formed into a desired thickness. The attachment to the substrate may be performed, for example, by attaching the molding material composition from the surface and back of the substrate approximately simultaneously, or by attaching the molding material composition to the surface side of the substrate and then to the back side. In the case where the substrate is a conductive substrate (e.g., a current collector such as a current collector foil), the substrate may have a conductive coating on the surface in contact with the molding material composition. As the conductive coating, for example, carbon coating, ITO, and metal plating can be cited. The conductive coating may be applied to the current collector foil side, or may be applied or sprayed on the component side. In the case where the conductive coating has sufficient strength and conductivity, it can also be used as a conductive substrate (e.g., a current collector) by itself. The current collector may be metal or non-metal as the main body. Non-metallic current collectors can be made into conductive current collectors by mixing conductive carbon materials and metal materials in polymers such as polyethylene, polypropylene, cellulose, and rubber. In the case where the substrate is an insulating substrate (such as a separator substrate such as a porous diaphragm), the substrate may contain a polymer as the main body. As substrates containing polymers as the main body, for example, polyethylene, polypropylene, cellulose, rubber, etc. can be cited. In addition, after the molding material composition is attached to the substrate, the component and the substrate do not need to be cut or opened together. In addition, the method for manufacturing a component for an electrochemical device of the present invention may include a step of peeling the molding material composition already attached to the substrate from the substrate.

[0159] <De-plasticization by drying operation>

[0160] The method for manufacturing a component for an electrochemical device of the present invention may include a step of removing moisture by a drying operation to form a non-plasticized state. The drying operation may be performed before or after the molding material composition is manufactured (e.g., shaped) into the final shape when the component is configured in the device. The drying operation may be performed, for example, in a vacuum, a low humidity environment, or by heating. Vacuum refers to a degree of decompression sufficient to remove the moisture contained in the component, and the decompression may be, for example, to 100Pa, preferably 10Pa, and more preferably 1Pa. A low humidity environment refers to a humidity sufficient to remove the moisture contained in the component, and may be, for example, an environment with a relative humidity of less than 80%, less than 70%, less than 60%, less than 50%, less than 40%, less than 30%, less than 20%, or less than 10% at room temperature. Heating refers to placing the component at a temperature at which the moisture contained in the component is removed and the component does not change its properties. The temperature may be, for example, above 50°C, preferably above 80°C, more preferably above 100°C, and may be, for example, below 300°C, preferably below 200°C, and more preferably below 150°C. In addition, the drying operation can be carried out in a state where the molding material composition is not in contact with the current collecting foil. In addition, the drying operation can be carried out in a state where the molding material composition is not in contact with the porous diaphragm. In the case where the components (such as electrodes) of the electrochemical device in the plasticized state are made into the final shape and then dried, the drying operation performed by the drying furnace which is usually present in the previous stage can be omitted. In this case, since the shaping is carried out in the plasticized state, it is not necessary to apply excessive force to make the final shape, and the damage of the component can be prevented.

[0161] <Recovery of plasticized state after deplasticization>

[0162] The method for manufacturing a component for an electrochemical device of the present invention may include a step of restoring the plasticized state by adding water or humidifying again after the molding material composition becomes a non-plasticized state. Adding water can be performed under conditions such as 25°C, dripping or spraying for 1 second. Humidification can be performed under conditions such as 25°C and 99% RH. The molding material composition can be manufactured (e.g., shaped) into the final shape when the component is configured in the device after restoring the plasticized state.

[0163] <Storage of electrochemical device components>

[0164] When the components for the electrochemical device of the present invention (such as electrodes, etc.) are stored, the one with less amount of plasticizer (PS) is less likely to stick to each other, so it is preferred. The operation of reducing the plasticizer (PS) for storage does not need to be performed until the polymer is no longer liquid or gel-like. The operation of reducing the plasticizer (PS) is preferably reduced to less than 90% relative to the total amount of the added plasticizer (PS), and further preferably reduced to less than 80%. However, in the case of using only ionic liquid as the plasticizer (PS), such an operation of reducing the plasticizer (PS) cannot be performed. In the case where the adhesion of the components for the electrochemical device is very strong, it is preferred to sandwich a plastic film during storage. There are no special requirements for the material, and PE, PP, PET, PTFE, etc. are preferred, and they can be subjected to release treatment and concave-convex treatment.

[0165] <Manufacturing method including recycling of scraps>

[0166] The manufacturing method of the component for an electrochemical device of the present invention may include the step of using the scraps of the molding material composition produced in the process of shaping the molding material composition, and manufacturing the next component again. The molding material composition used in the present invention can suppress irreversible quality changes during the manufacturing process by having plasticity and self-supporting properties, so the scraps of the molding material composition can be used again to manufacture the next component. In the case of reusing the scraps of the molding material composition, from a quantitative aspect, it is preferably dried to the moisture balance of the environment and then water is added again. In the case of adding water to the component again, it is preferably possible to use operations such as spraying, dripping, electrostatic spraying, and dipping to increase the humidity of the environment. In the case of adding ionic liquids, organic solvents, etc. to the component, it is preferably possible to use operations such as spraying, dripping, electrostatic spraying, and dipping.

[0167] <Conditions of the manufacturing method>

[0168] The manufacturing method of the electrochemical device component of the present invention (e.g., the manufacturing operation of the battery component) can be implemented in a normal humidity environment or in a dry environment (dry room, glove box). When implemented in a dry environment below 50% RH, it is preferred to add an ionic liquid. From the viewpoint of suppressing the loss of water, it is preferably implemented in a low temperature and high humidity environment.

[0169] (Method for recycling components for electrochemical devices)

[0170] The molding material composition used in the present invention can suppress irreversible quality changes during the manufacturing process by having plasticity and self-supporting properties, so it is possible to use, for example, a molding material composition in the middle of the manufacturing process (for example, a molding material composition already attached to a substrate, a molding material composition in a non-plasticized state, and scraps of a molding material composition) to reuse the electrochemical device component. The reuse method of the electrochemical device component may include, for example, a step of peeling off the molding material composition already attached to the substrate from the substrate. In addition, the reuse method of the electrochemical device component may include, for example, a step of restoring the plasticized state by adding water or humidifying again after the molding material composition becomes a non-plasticized state. In addition, the reuse method of the electrochemical device component may include, for example, using the scraps of the molding material composition produced in the process of shaping the molding material composition, and manufacturing the next component again.

[0171] (Method for manufacturing electrochemical device)

[0172] The method for producing an electrochemical device of the present invention includes the step of obtaining the member by the above-mentioned method for producing or recycling the member for an electrochemical device.

[0173] (Components for electrochemical devices)

[0174] The electrochemical device component of the present invention is obtained by the manufacturing method or recycling method of the electrochemical device component described above. As the electrochemical device component of the present invention, for example, electrodes (such as positive electrodes, negative electrodes), insulating layers (such as insulating films), and adhesive layers can be cited. The electrochemical device component is preferably an electrode or an insulating layer. The electrode also includes an air electrode of an air battery. The insulating layer can be used as an insulating layer of a storage device such as a lithium ion battery, and can also be attached to glass or the like formed with a conductive ITO (indium tin oxide) layer for use in dye-sensitized solar cells, electrochromic devices, etc. The insulating layer can be used in a plasticized state for device assembly, or it can be dried and used in a non-plasticized state. It is also a preferred method to assemble the device in an uncrosslinked state and finally crosslink it with ultraviolet rays, heat, etc.

[0175] (Electrochemical Device)

[0176] The electrochemical device of the present invention includes the above-mentioned electrochemical device component. As the electrochemical device of the present invention, for example, non-aqueous or aqueous primary batteries such as lithium primary batteries, manganese primary batteries (such as manganese-zinc primary batteries, manganese-lithium primary batteries); lithium ion secondary batteries (non-aqueous, aqueous), lithium metal secondary batteries, sodium ion secondary batteries, potassium ion secondary batteries, magnesium secondary batteries, aluminum secondary batteries and other non-aqueous or aqueous secondary batteries; air batteries; solar cells such as dye-sensitized solar cells; capacitors such as double-layer capacitors and lithium ion capacitors; electrochromic display devices; electrochemical luminescent elements; double-layer transistors; electrochemical actuators. The electrochemical device is preferably a non-aqueous secondary battery, and more preferably a lithium ion secondary battery.

[0177] The electrochemical device of the present invention may include, for example, an electrode as a member for the electrochemical device. The electrochemical device of the present invention may include an electrode obtained by the manufacturing method or recycling method described later and an electrode (counter electrode). The counter electrode may include, for example, at least one selected from alkali metals (e.g., lithium, sodium, potassium, rubidium, cesium), alkaline earth metals (e.g., beryllium, magnesium, calcium, strontium, barium), metal aluminum, and silver.

[0178] When the electrochemical device of the present invention is a Li-ion battery, in the process of manufacturing the Li-ion battery, when using a perforated current collector foil, vertical pre-doping can be performed by configuring a Li metal electrode in addition to the positive electrode and the negative electrode inside the battery cell. This is an effective method when using an active material with an initial irreversible capacity.

[0179] The electrochemical device of the present invention may be any of an aqueous electrochemical device or a non-aqueous electrochemical device. As an aqueous electrochemical device, for example, an electrochemical device containing water in the electrolyte (for example, aqueous lithium ion secondary batteries, manganese zinc primary batteries and other aqueous batteries) can be cited. As a non-aqueous electrochemical device, for example, an electrochemical device in which the electrolyte is dissolved in an organic solvent and does not contain water (for example, non-aqueous lithium ion secondary batteries, lithium primary batteries, manganese lithium primary batteries and other non-aqueous batteries) can be cited. Aqueous electrochemical devices and non-aqueous electrochemical devices can be, for example, non-aqueous electrochemical devices in which the carrier ions are at least one of alkali metal ions (for example, lithium ions, sodium ions, potassium ions), alkaline earth metal ions (for example, beryllium ions, magnesium ions, calcium ions), aluminum ions, silver ions, organic nitrogen cations (for example, triethylmethylammonium 1-ethyl-3-methylimidazolium) and halide anions (for example, bromide ions, iodide ions).

[0180] Example

[0181] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples.

[0182] In the following description, "bendable" means that even when the member is wound around a cylinder having a constant diameter and bent, no breakage is observed. "Self-supporting property" and "plasticity" are as described above.

[0183] The following is an experimental example of a lithium ion battery and a manganese battery, but the same effects are achieved in other devices.

[0184] (Example 1: Production and Evaluation of Electrode Sheet Using Polyethylene Oxide (PEO))

[0185] In a laboratory with an air temperature of 25°C and a humidity of 90% RH, 100 g of lithium cobalt oxide (Cellseed C manufactured by Nippon Chemical Industry Co., Ltd., with an average particle size of 20 μm) as an active material, 3 g of acetylene black as a conductive aid, 8 g of ion exchange water as a processing solvent, 1 g of polyethylene oxide (PEO) (Sigma-Aldrich) with a weight average molecular weight of 1 million as polymer P1, and 1 g of polytetrafluoroethylene (PTFE) (Sigma-Aldrich) as a fibrous material were weighed and put into a mortar and mixed to form a uniform electrode composition. Take 1 g of the electrode composition and use a SUS hand roller with a diameter of 3 cm on a release polyethylene terephthalate (PET) film to form a sheet (electrode sheet 1-1) with a thickness of 200 μm. It was evaluated immediately, and the sheet had self-supporting properties and plasticity and could be bent with a diameter of 2 mm. At this time, polyethylene oxide was an aqueous solution, which was considered to contribute to the flexibility of the electrode. The thickness of the sheet end portion tends to be slightly thinner than the central portion, and the average thickness at a position 5 mm from the end portion is 197 μm. The end portion can be cut off as needed. The cut end portion can be reused to manufacture an electrode.

[0186] (Example 2: Production, Evaluation and Regeneration of Electrode Sheet Using PEO-Based Polymer)

[0187] In a laboratory at 25°C and 90%RH, 100g of lithium cobalt oxide, 3g of acetylene black, 8g of ion exchange water, 1g of a random copolymer of ethylene oxide and propylene oxide (molar ratio 9:1) with a weight average molecular weight of 1 million as polymer P1, and 1g of PTFE were weighed and put into a mortar and mixed to form a uniform electrode composition. Take 1g of the electrode composition, sandwich it between a release PET film, and use a SUS hand roller with a diameter of 3cm to obtain a sheet with an average thickness of 2mm (electrode sheet 2-1). It was immediately evaluated and the results showed that the sheet had a slight adhesiveness, self-supporting properties and plasticity. Furthermore, it was squeezed with a hand roller to form a sheet with an average thickness of 200μm (195~205μm) (electrode sheet 2-2), which could be bent with a diameter of 2mm. At this time, the copolymer is an aqueous solution, which is believed to contribute to the flexibility of the electrode.

[0188] Electrode sheet 2-2 was placed in a laboratory with an air temperature of 25°C and a humidity of 55%. The surface felt dry in about 1 minute and the adhesion decreased. It was left in this state for 1 day. The thickness did not change, and the weight decreased by 7% compared to the initial weight. It was considered that 99% of the added water had evaporated (comparison electrode sheet 2-2), and the polyethylene oxide was judged to be in an unplasticized state. When it was attempted to bend it, it broke at an inner angle of about 120° before being wound around a cylinder. The density of the electrode sheet before breaking in a dry state was 3 g / cm 3 The volume fraction of the filler including lithium cobalt oxide and acetylene black in the electrode sheet was 61 volume %. Then, the density can be further increased by pressing using a high-pressure roll press.

[0189] The electrode sheet 2-2 was further pressed with a roller at a linear pressure of 200 N / cm until the average thickness was reduced to 50 μm (49 to 51 μm) (electrode sheet 2-3), and then attached to a conductive polyethylene film (surface resistance 10 μm) with a thickness of 50 μm containing conductive carbon prepared separately as a current collector. 4 Ω / sq. or less), and a lithium-ion battery positive electrode (positive electrode 2-4) was manufactured.

[0190] In a laboratory with a temperature of 25°C and a humidity of 55%, the electrode sheets 2-1, 2-2, 2-3 and the positive electrode 2-4 were cut with scissors, and they were able to be cut straight into two pieces. At this time, no small pieces such as fine powder were generated, and the molding material did not adhere to the scissors. They were overlapped again and stretched with a hand roller, and as a result, they were combined and regenerated into the same sheet as the original.

[0191] (Comparative Example 1: Evaluation of Sheet from which Water Has Volatilized)

[0192] The same method as in Example 2 was used to cut the comparative electrode sheet 2-2 with scissors. As a result, cracks occurred in the parts other than the cut parts, and a straight cut surface could not be obtained. Fine powder was also produced. The scissors also had fine powder attached. The pieces that were divided into several parts were collected and stretched with a hand roller. Not only did they not merge, but they became more fragmented.

[0193] (Comparative Example 2: Preparation and Evaluation of Slurry-Coated Electrode)

[0194] The electrodes were made using the slurry coating method commonly used in the manufacture of lithium-ion batteries and double-layer capacitor electrodes. Although the electrode slurries using lithium cobalt oxide, graphite, and activated carbon all showed plasticity, they could not be confirmed to be self-supporting. The electrode slurry using graphite was coated on an aluminum foil with a thickness of 25 μm, and an attempt was made to cut it with scissors in an undried state, resulting in a large amount of slurry attached to the blade. In addition, the slurry flowed out of the collector foil from the cut.

[0195] (Comparative Example 3: Preparation and Evaluation of Slurry-Coated Dry Electrode)

[0196] The coated electrode of Comparative Example 2 was dried in an oven at 60° C., and an attempt was made to peel off 5 mm of the electrode composite material from the end of the electrode in the dry state. The interface between aluminum and the composite material was peeled off with a plastic scraper, and fine powder was generated by the peeling and adhered to the surroundings.

[0197] (Example 3: Evaluation of Adhesion of Electrode Sheet Using PEO-Based Polymer)

[0198] The electrode sheet 2-3 of Example 2 was cut into a size of 5 cm square, placed on an aluminum foil with a thickness of 25 μm in a laboratory with an air temperature of 25°C and a humidity of 55%, and the entire surface of the electrode sheet 2-3 was gently squeezed from above with a hand roller. As a result, the electrode sheet 2-3 was tightly fitted with the aluminum foil. The thickness of the end of the sheet was slightly thinner, so a circle of notch that did not reach the collector foil was added at 5 mm on the periphery. The end was clamped with tweezers and peeled off. As a result, the peripheral molding material could be removed in the shape of a square frame without producing small pieces or fine powder (positive electrode 3). The electrode sheet that would become 4 cm square was further placed in a laboratory with an air temperature of 25°C and a humidity of 55% for 24 hours. The result confirmed that the weight was reduced due to water volatilization as in Example 1, but the electrode sheet 2-3 and the aluminum foil remained tightly fitted.

[0199] (Example 4: Production and Evaluation of Electrode Sheets Using Polymers Other Than PEO)

[0200] The polymer P1 was changed to poly-2-ethyl A sheet was prepared in the same manner as in Example 1 except that oxazoline (Sigma-Aldrich) was used. The sheet was immediately evaluated and found to be self-supporting and bendable with a diameter of 2 mm.

[0201] (Example 5: Production and Evaluation of Electrode Sheet Containing Second Polymer (P2))

[0202] Further, 1 g of carboxymethyl cellulose (CMC) as a second polymer (polymer P2) was added. Otherwise, the same method as in Example 2 was used to prepare a lithium ion battery positive electrode (positive electrode 5) having a thickness of 50 μm. Positive electrodes 2-4 and 5 of Example 2 were vacuum dried at 40°C for 48 hours, and a lithium ion battery was prepared with a configuration in which the counter electrode was Li metal and the electrolyte was LiFSI / EC=1 / 4. The battery was charged and discharged at a rate of 1C. As a result, the positive electrode capacity retention rate after 200 cycles relative to the initial capacity was 91% for positive electrode 2-4 and 95% for positive electrode 5, and the electrode sheet containing polymer P2 was superior. It is believed that this is because the component (polymer P2) that does not dissolve and swell after immersion in the electrolyte functions as a protective film on the surface of the positive electrode active material.

[0203] (Example 6: Production and evaluation of electrode sheet using deliquescent polymer)

[0204] A dimethylamine-epichlorohydrin-ethylenediamine copolymer (Sigma-Aldrich) with a weight-average molecular weight of 75,000 was used as polymer P1. The polymer exhibits deliquescent properties and absorbs moisture equivalent to 15% by weight of its own weight in a laboratory at an air temperature of 25°C and a humidity of 55%, becoming a spontaneously plasticized aqueous solution. 9 g of the spontaneously plasticized polymer solution, 100 g of lithium cobalt oxide, 3 g of acetylene black, and 1 g of PTFE were weighed and placed in a mortar and mixed to form a uniform electrode composition. 1 g of the electrode composition was separated and taken out, sandwiched between a release PET film, and a SUS hand roller with a diameter of 3 cm was used to obtain a sheet (electrode sheet 6) with an average thickness of 2 mm. The evaluation was immediately performed, and the result showed that the sheet had a slight adhesiveness, self-supporting properties, and plasticity. Furthermore, it was squeezed with a hand roller to form a sheet (electrode sheet 6-2) with an average thickness of 200 μm (195 to 205 μm), which could be bent with a diameter of 2 mm. The copolymer is an aqueous solution and is believed to contribute to the flexibility of the electrode. When the solution was left for 24 hours, there was no change in weight and the sheet remained flexible.

[0205] (Example 7: Production and Evaluation of Electrode Sheet Using Ionic Liquid)

[0206] The experiment was conducted in a dry room with humidity maintained at a dew point temperature of -40°C or less and an air temperature of 25°C. The raw materials used were thoroughly dried in advance. 100 g of lithium cobalt oxide, 3 g of acetylene black, 11 g of DEME-TFSI (N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethanesulfonyl)imide) as a water-insoluble ionic liquid, 1 g of a random copolymer of ethylene oxide and propylene oxide with a weight average molecular weight of 1 million (molar ratio 9:1), and 1 g of PTFE were weighed and put into a mortar and mixed to prepare a uniform electrode composition. The electrode composition was taken and formed into a sheet (electrode sheet 7) with an average thickness of 60 μm on a flat SUS table using a SUS roller with a diameter of 3 cm. The sheet has self-supporting properties and plasticity and can be bent with a diameter of 1 mm. The moisture content of the sheet was measured by a Karl Fischer titrator and the result was 46 ppm.

[0207] In order to remove moisture more carefully, the electrode sheet 7 was vacuum dried at 100° C. for 24 hours. The moisture content of the sheet was measured with a Karl Fischer titrator and found to be 4 ppm.

[0208] (Example 8: Combined use of water and ionic liquid, and cross-linking of electrodes)

[0209] In a sealed mixer, 100 g of lithium cobalt oxide, 3 g of acetylene black, 6 g of water-insoluble ionic liquid (N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethanesulfonyl)imide), 4 g of ion exchange water, 1 g of a random copolymer of ethylene oxide-allyl glycidyl ether with a weight average molecular weight of 1,000,000 (molar ratio 9:1), 1 g of PTFE, and 50 mg of Percumyl D as a thermal polymerization initiator were mixed at room temperature to prepare a uniform electrode composition. The electrode composition was taken, sandwiched between a release PET film, and formed into a sheet (sheet 8-1) with a thickness of 200 μm using a SUS hand roller with a diameter of 3 cm. The sheet had a slight adhesiveness, self-supporting properties, and plasticity, and could be bent with a diameter of 2 mm.

[0210] Sheet 8-1 was placed in a laboratory with an air temperature of 25°C and a humidity of 55%. As a result, the surface felt dry in about 1 minute and the adhesiveness decreased. Furthermore, in order to dehydrate and cross-link by heating, the sheet was vacuum dried in a vacuum dryer at 150°C for 30 minutes. The weight was reduced by 3.5%, and it was considered that the sheet (comparison sheet 8-2) in which almost 100% of the added water was volatilized, was judged to be in a state of being plasticized by the polymer ionic liquid. Comparison sheet 8-2 maintained its flexibility and could be bent with a diameter of 5 mm. When cut with scissors, it was possible to cut it straight into two pieces without producing fine powder, etc., overlapped them again, and stretched them with a hand roller, but they did not merge. It can be confirmed that although the electrode strength is improved by cross-linking, it cannot be merged because the fluidity disappears.

[0211] The cross-linking operation is preferably carried out when the polymer (P1) is in a plasticized state, and can be carried out before the device is assembled as in this embodiment, or can be carried out after the device is assembled by heating the device itself.

[0212] (Example 9: Production and evaluation of electrode sheet using cellulose nanofibers)

[0213] In a laboratory with an air temperature of 25 degrees and a humidity of 90% RH, 100g of lithium cobalt oxide, 3g of acetylene black, 8g of ion exchange water, 1g of a random copolymer of ethylene oxide and propylene oxide with a weight average molecular weight of 1 million (molar ratio 90:5:5), and 2g of cellulose nanofibers (nanoforest-S Chuetsu Pulp Industry) were weighed and put into a mortar and mixed to form a uniform electrode composition. Take 1g of the electrode composition, sandwich it in a release PET film, and use a SUS hand roller with a diameter of 3cm to obtain a sheet with a thickness of 2mm (electrode sheet 9-1). It was evaluated immediately and the result showed that the sheet had a slight adhesiveness, self-supporting properties and plasticity. Furthermore, it was squeezed with a hand roller to form a sheet with a thickness of 200μm (sheet 9-2), which could be bent with a diameter of 2mm. Polyethylene oxide is an aqueous solution, which is believed to contribute to the flexibility of the electrode.

[0214] (Example 10: Spraying to the electrode)

[0215] A small amount of water was sprayed on the comparative sheet 2-2 obtained in Example 1 with a sprayer, and the electrode absorbed the sprayed water and recovered its flexibility. The sheet could be bent with a diameter of 2 mm. The weight of the electrode was measured, and it was confirmed that the weight equivalent to 80% of the initial water content was recovered.

[0216] (Example 11: Adding water to the electrode again)

[0217] The electrode fragments without aggregation obtained in Comparative Example 1 were collected, ion exchange water in an amount corresponding to the lost water was added dropwise, and mixed again. As a result, an electrode composite material identical to the initial one was obtained, and a sheet identical to sheet 1 could be manufactured.

[0218] (Example 12: Impregnation of Electrolyte into Electrodes)

[0219] A small amount of a separately prepared 1M LiTFSI / propylene carbonate solution was added to the comparative sheet 2-2 obtained in Example 1 to the extent that the electrolyte did not overflow from the electrode. When the electrolyte was confirmed to have penetrated into the electrode, the flexibility of the electrode was restored and it was possible to bend it by 2 mm. Since the random copolymer of ethylene oxide-propylene oxide (molar ratio 9:1) is soluble in propylene carbonate, it was confirmed that it could be plasticized in the electrolyte and maintain flexibility even in the device.

[0220] (Example 13: Graphite Electrode)

[0221] In a laboratory with an air temperature of 25 degrees and a humidity of 90% RH, 40g of graphite (604A manufactured by Nippon Carbon Co Ltd.) as the negative electrode active material of the lithium ion battery, 7g of ion exchange water, 1g of a random copolymer of ethylene oxide and propylene oxide with a weight average molecular weight of 1 million (molar ratio 9:1), and 0.2g of PTFE were weighed and put into a mortar and mixed to form a uniform electrode composition. Take 1g of the electrode composition, sandwich it between a release PET film, and use a SUS hand roller with a diameter of 3cm to obtain a sheet with an average thickness of 2mm (electrode sheet 13-1). Immediately evaluated, the result showed that the sheet had a slight adhesiveness, self-supporting properties and plasticity. Furthermore, it was squeezed with a hand roller to form a sheet with an average thickness of 200μm (195~205μm) (electrode sheet 13-2), which can be bent with a diameter of 2mm. This was further pressed with a hand roller until the average thickness was reduced to 50 μm (49 to 51 μm) (electrode sheet 13 - 3 ), and bonded to a 25 μm thick electrolytic copper foil to produce a lithium ion battery negative electrode (negative electrode 13 - 3 ).

[0222] The density of the electrode in a dry state is 1.74 g / cm 3 The volume fraction of the filler in the electrode is only 70 vol% based on graphite. The electrode can then be further pressed by a high-pressure roller press, thereby increasing the density.

[0223] (Example 14: Addition of solid lubricant)

[0224] A molding material was prepared in the same manner as in Example 1 except that 5 g of graphite powder (KS4 manufactured by TIMCAL) was added as a solid lubricant. The molding material was pressed with a roller having a linear pressure of 200 N / cm as in Example 1, and a sheet having an average thickness of 45 μm (44 to 46 μm) was obtained. By adding a solid lubricant, a thin sheet can be produced with the same processing force.

[0225] (Example 15: Electrode using nano-sized Si)

[0226] 10g of silicon powder (average particle size 100nm) as the negative electrode active material of lithium ion battery, 8g of ion exchange water, and 1g of random copolymer of ethylene oxide-propylene oxide with a weight average molecular weight of 1 million (molar ratio 9:1) were weighed and put into a mortar and mixed to form a uniform electrode composition. 1g of the electrode composition was taken, sandwiched between a release PET film, and a SUS hand roller with a diameter of 3cm was used to obtain a sheet with an average thickness of 2mm (electrode sheet 15-1). It was immediately evaluated and the results showed that the sheet had a slight adhesiveness, self-supporting properties and plasticity. Furthermore, it was squeezed with a hand roller to form a sheet with an average thickness of 200μm (195~205μm) (electrode sheet 15-2), which could be bent with a diameter of 2mm.

[0227] (Example 16: Activated carbon and carbon nanotubes (CNT))

[0228] 10 g of activated carbon MSP-20 (Kansai Thermochemical) and 0.1 g of carbon nanotubes (CNTs) (manufactured by Zeon Nano Technology Co., Ltd., ZEONANO SG101, average diameter: 4 nm, average length: 400 μm, BET specific surface area: 1150 m) as a component of both a conductive material and a fibrous substance were weighed. 2 / g), 11g of DEME-BF4 (N,N-diethyl-N-methyl-N-(2-methoxyethyl)-tetrafluoroborate) as a water-soluble ionic liquid, and 1g of a random copolymer of ethylene oxide and propylene oxide with a weight average molecular weight of 1 million (molar ratio 9:1) are put into a mortar and mixed to form a uniform electrode composition. Take 1g of the electrode composition, sandwich it between a release PET film, and use a SUS hand roller with a diameter of 3cm to obtain a sheet with an average thickness of 2mm (electrode sheet 16-1). It was immediately evaluated and the results showed that the sheet had slight adhesiveness, self-support and plasticity. Furthermore, it was squeezed with a hand roller to form a sheet with an average thickness of 200μm (195~205μm) (electrode sheet 16-2), which can be bent with a diameter of 2mm. Such a sheet can be used as a capacitor electrode, a fuel cell electrode, an air battery electrode, an electrochemical actuator, etc.

[0229] Furthermore, although there were fibers longer than the thickness of the sheet, it was not confirmed that the fibers protruded from the electrodes.

[0230] (Example 17: Fabrication of Insulating Layer)

[0231] 40 g of Aerosil 380 (registered trademark) (manufactured by EVONIK) as a nano-sized filler, 10 g of a molecular weight 1 million ethylene oxide-propylene oxide random copolymer (molar ratio of 90:10), and 70 g of 1-butyl-3-methylimidazolium tetrafluoroborate as a solvent were weighed and put into a mortar and mixed to prepare a uniform insulating layer composition. The same method as in Example 1 was used to obtain a 50 μm sheet (insulating layer 17). The sheet had self-supporting properties and plasticity and could be bent with a diameter of 1 mm.

[0232] Such an insulating layer can be used as an insulating layer of a power storage device such as a lithium ion battery, and can also be attached to glass having a conductive ITO (indium tin oxide) layer formed thereon, and used for dye-sensitized solar cells, electrochromic devices, and the like.

[0233] (Example 18: Crosslinking of Insulating Layer)

[0234] 40 g of Aerosil R711 (registered trademark) (manufactured by EVONIK, methacryloyloxysilane treated) as a nano-sized filler, 20 g of alumina, 10 g of a random copolymer of ethylene oxide-propylene oxide-allyl glycidyl ether with a molecular weight of 1 million (molar ratio of 90:5:5), 70 g of water as a solvent, and 500 mg of Irg651 as an ultraviolet crosslinking agent were weighed, and the same process as in Example 1 was performed to obtain a 50 μm sheet (insulating layer 18). The sheet is self-supporting and can be bent with a diameter of 1 mm. The insulating layer 1 is sandwiched between release PET films without drying, and is irradiated with ultraviolet rays in a plastic state to crosslink it, thereby obtaining a crosslinked insulating layer 18.

[0235] The insulating layer 18 was cut into strips with a width of 1 cm, and stretched without drying to maintain the plastic state. As a result, it broke when it was stretched by 5%. Similarly, the cross-linked insulating layer 18 was stretched, and it did not break even when it was stretched by 10%. The cross-linked insulating layer is less likely to break under mechanical pressure, and a higher effect of preventing internal short circuits in the device can be expected.

[0236] The insulating layer can be kept in a plasticized state for device assembly, or can be dried and used in a non-plasticized state. It is also a preferred method to assemble the device in an uncrosslinked state and finally crosslink it using ultraviolet light, heat, etc.

[0237] (Example 19: Preparation of an insulating layer containing a solid electrolyte)

[0238] 120 g of LAGP (Li 1.5 Al 0.5 Ge 1.5 P3O 12 ) powder (average particle size 1 μm, density 3.0 g / cm 3 ), 4.5 g of a molecular weight of 1 million ethylene oxide-propylene oxide random copolymer (molar ratio of 90:10), 42 g of 1-methyl-3-propylimidazolium bis(trifluoromethanesulfonyl)imide (Sigma-Aldrich) as a solvent, and 3 g of PTFE were put into a mortar and mixed to form a uniform insulating layer composition. The same method as in Example 17 was used to obtain a 50 μm sheet (insulating layer 19). The sheet has self-supporting properties and plasticity and can be bent with a diameter of 1 mm. The volume fraction of the filler in the sheet is 53 vol% based on LAGP alone. The ionic conductivity of the sheet was measured by the AC impedance method, and the result was 1.0×10 -3 S / cm ion conductivity, suitable for use as an insulating layer for lithium-ion batteries.

[0239] (Example 20: Alkaline production example)

[0240] 70g of strongly alkaline lithium nickelate (Sigma-Aldrich), which is a positive electrode active material for lithium ion batteries, 3g of acetylene black, 8g of ion exchange water, 1g of carboxymethyl cellulose (BSH-12 manufactured by Daiichi Industrial Pharmaceutical Co., Ltd.), and 1g of PTFE were weighed and put into a mortar and mixed to form a uniform electrode composition. Take 1g of the electrode composition, sandwich it between a release PET film, and use a SUS hand roller with a diameter of 3cm to obtain a sheet (electrode sheet 20-1) with an average thickness of 2mm. It was evaluated immediately and the result showed that the sheet was slightly adhesive, self-supporting and plastic. It was further squeezed with a hand roller to form a sheet (electrode sheet 20-2) with an average thickness of 200μm (195~205μm), which can be bent with a diameter of 2mm. CMC is an aqueous solution and is believed to contribute to the flexibility of the electrode.

[0241] The sheet was attached to a 25 μm thick aluminum foil, left for about 10 minutes, and then peeled off. As a result, the surface of the aluminum foil was corroded by alkali and turned white. When used as a lithium ion battery electrode, this will cause an increase in resistance.

[0242] When the same operation was performed after the sheet was dried and then pasted, the aluminum foil did not turn white.

[0243] When the same operation was performed after changing the processing solvent to an ionic liquid (DEME-TFSI (N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(trifluoromethanesulfonyl)imide)), the aluminum foil did not turn white.

[0244] (Example 21: Pasting of electrode and insulating layer)

[0245] The electrode sheet 7 produced in Example 7 and the insulating layer 19 produced in Example 19 were bonded together in a plasticized state so as not to allow air bubbles to enter, and the two were bonded well to obtain an integrated sheet.

[0246] (Example 22: Preparation and compounding of low-density electrodes)

[0247] The thickness is set to 100 μm, and the first electrode sheet (electrode sheet 22-1) is produced in the same manner as in Example 1. Furthermore, the amount of lithium cobalt oxide is set to half that of Example 1, i.e., 50 g, to produce a second electrode sheet (electrode sheet 22-2). The first electrode sheet is pasted on an aluminum foil with a thickness of 25 μm, and the second electrode sheet is placed on it, so that they are tightly fitted and integrated without the entry of bubbles. In this way, a composite electrode sheet with different densities between the upper and lower layers is manufactured. At this time, the first electrode sheet can be pasted after it is dried. The second electrode sheet was dried, and the measured density was 2.64 g / cm 3Therefore, the volume fraction of the filler in the electrode, including lithium cobalt oxide and acetylene black, is 61 Vol% in the lower layer and 47 Vol% in the upper layer. Such an electrode, whose density decreases as it moves away from the current collector, has an ion conduction resistance lower than the electrode thickness, which is beneficial for improving the high output and operating speed of the device.

[0248] (Example 23: Manufacturing method of extruding into blocks and slicing)

[0249] The composition of Example 2 is used to continuously discharge a cylindrical shape of 15 mm in diameter from a twin-screw extruder (L / D=30) having a metal mouth of 15 mm in diameter to manufacture a molding material composition. A steel cutter is set to move therefrom in a direction transverse to the cylinder, and the cylinder is continuously cut into a disc shape of 200 μm in thickness and 15 μm in diameter to make an electrode sheet. If the metal mouth is changed, a hollow cylinder such as macaroni can also be manufactured. In the case of concern about the generation of metal powder due to friction between metals, the metal mouth and the cutter can be set to ceramic or plastic.

[0250] (Example 24: Manufacturing method of extruding into a tube and cutting)

[0251] The same extruder as in Example 23 was used, and the outlet was changed to a ring-shaped metal port with an outer diameter of 50 mm and an inner diameter of 49 mm, and extrusion was performed to form a tube with a film thickness of 500 μm. A steel cutter was set at a position about 100 mm from the extrudate extruded from the metal port, and one position of the tube cross section was continuously cut. By continuously opening the cut tube, a sheet of the same thickness (494 to 506 μm) with the same thickness deviation in the center and the end was obtained. In the case of concern about the generation of metal powder due to friction between metals, the metal port and the cutter can be set to ceramic or plastic.

[0252] (Example 25: Made with multiple strands)

[0253] The same extruder as in Example 23 was used, the die outlet was changed to 20 cylindrical die outlets with a diameter of 300 μm and arranged at intervals of 4 mm, and the die outlet was sandwiched between two metal rollers (roller diameter 30 mm, linear pressure 200 N) for shaping, and a sheet with an average thickness of 32 μm was produced. In the case of concern for the generation of metal powder due to friction between metals, the roller surface can be made of ceramic or plastic.

[0254] (Example 26: Device Manufacturing Example)

[0255] While winding an aluminum foil with a thickness of 25 μm, the electrode sheet 2-3 of Example 2, the insulating layer 18 of Example 18, the electrode sheet 13-3 of Example 13, and the rolled copper foil with a thickness of 25 μm on a metal rod with an outer diameter of 2 mm, a winding body with a diameter of 10 mm is obtained. Since each sheet is in a plasticized state, it is soft and not damaged during winding. The winding body is stored in an aluminum laminate package and flattened by gently squeezing it from the outside. Move it to a vacuum dryer at 100°C and dry it for 6 hours. 1M LiPF6 EC / DMC (30 / 70) as an electrolyte is injected into it, sealed under vacuum, and a lithium ion battery is made. It is charged and discharged at 4.2V~3.0V and a rate of 0.1C, and the result is a reversible capacity of 145mAh / g per unit positive electrode active material, which can be seen as a battery.

[0256] (Example 27: Manganese battery manufacturing example)

[0257] As an electrolyte, an aqueous solution containing 20 wt% zinc chloride and 5 wt% ammonium chloride was prepared. 100 parts of manganese dioxide (MnO2, 99.5%, Fujifilm Wako Pure Chemical Industries, Ltd., 133-09681), 6 parts of acetylene black (DENKA BLACK granules, manufactured by Denka Kogyo Co., Ltd.), 2 parts of a random copolymer of ethylene oxide and propylene oxide (molar ratio 9:1) with a weight average molecular weight of 1 million as polymer P1, and 2 parts of PTFE, 40 parts of the above electrolyte were put into a mortar and fully kneaded to prepare a uniform electrode composition. 1 g of the electrode composition was taken, sandwiched between a release PET film, and a SUS hand roller with a diameter of 3 cm was used to obtain a self-supporting sheet with an average thickness of 2 mm. The sheet was immediately evaluated and the result showed that it had a slight adhesiveness, self-supporting properties, and plasticity. The sheet was further squeezed with a hand roller to form a sheet with an average thickness of 500 μm (497 to 503 μm), which could be bent with a diameter of 2 mm. round shape, attached to a graphite sheet ( A positive electrode was prepared on a sheet of paper (manufactured by Japan Kodo Paper Industry, trade name "TF4535", thickness 35 μm) cut into 16 mm circles as a separator, and immersed in the above-mentioned electrolyte so that it contains the electrolyte. Next, a zinc foil (manufactured by Nilaco Corporation, purity 99.99%, The positive electrode, separator, and negative electrode are stacked in this order to form a manganese battery, which is assembled into a 2032-type button battery. The voltage of the battery before discharge was measured and the result was 1.55V. When a 20Ω load was connected and discharged, the result was that it could be discharged at 40mA / cm 2 Discharge, the voltage at this time drops to 0.1V.

[0258] Industrial Applicability

[0259] According to the present invention, a method for producing and recycling an electrochemical device member can be provided, which is less likely to cause a problem of irreversible changes in the composition of the electrochemical device due to solvent reduction, moisture absorption, etc. during the production of the electrochemical device.

[0260] Furthermore, according to the present invention, it is possible to provide an electrochemical device member that is less likely to cause irreversible changes in the composition of the electrochemical device due to solvent reduction, moisture absorption, etc. during the manufacture of the electrochemical device, and an electrochemical device using the electrochemical device member.

Claims

1. A manufacturing method, which is a manufacturing method for a component for an electrochemical device, comprising the following steps: A step of subjecting the molding material composition to at least one shaping operation selected from the following group A; and The step of forming the molding material composition into a desired thickness and then attaching it to a substrate, The molding material composition has plasticity and self-supporting properties, comprises at least one filler (F), a plasticizer (PS), a polymer (P1) that can be plasticized by the plasticizer (PS), and a polymer (P2) that is plasticized by the plasticizer (PS) but is insoluble in an electrolyte, and substantially does not contain an organic solvent. The plasticizer (PS) is water, an ionic liquid or a mixture thereof, The polymer (P1) is a polymer containing ethylene oxide (EO) as a monomer unit, Oxazoline polymers, poly-N-vinylacetamide polymers, poly-N-vinylpyrrolidone, polyvinyl acetate, or epichlorohydrin-organic amine condensation products, The content of the plasticizer (PS) in the molding material composition is 3% by weight or more, Group A: extrusion, injection into a mold, stretching, compression molding, reducing thickness by pressurization, making thickness uniform by pressurization, cutting, drilling, cutting, bending into the final shape to be housed in an electrochemical device container, and pasting molding material compositions of different compositions together.

2. A manufacturing method, which is a manufacturing method for a component for an electrochemical device, comprising the following steps: A step of subjecting the molding material composition to at least one shaping operation selected from the following group A; and The step of forming the molding material composition into a desired thickness and then attaching it to a substrate, The molding material composition has plasticity and self-supporting properties, comprises at least one filler (F), a plasticizer (PS), and a polymer (P1) that can be plasticized by the plasticizer (PS), and substantially does not contain an organic solvent. The plasticizer (PS) is water, an ionic liquid or a mixture thereof, The polymer (P1) is a deliquescent polymer, The polymer (P1) is an epichlorohydrin-organic amine condensation product, The content of the plasticizer (PS) in the molding material composition is 3% by weight or more, Group A: extrusion, injection into a mold, stretching, compression molding, reducing thickness by pressurization, making thickness uniform by pressurization, cutting, drilling, cutting, bending into the final shape to be housed in an electrochemical device container, and pasting molding material compositions of different compositions together.

3. The manufacturing method according to claim 1 or 2, wherein: The polymer (P1) is a polymer that can also be plasticized by the electrolyte solvent (ES).

4. The manufacturing method according to claim 1, wherein: The polymer (P1) is a deliquescent polymer, and the polymer (P1) is an epichlorohydrin-organic amine polycondensate.

5. The manufacturing method according to claim 1, wherein: The polymer (P1) is a polymer containing ethylene oxide (EO) as a monomer unit, Oxazoline polymers, poly-N-vinylacetamide polymers, or epichlorohydrin-organic amine condensates.

6. The manufacturing method according to claim 1 or 2, wherein: The filler (F) contains the active substance (A).

7. The manufacturing method according to claim 1 or 2, wherein: The filler (F) contains an inorganic solid electrolyte.

8. The manufacturing method according to claim 1 or 2, wherein: The filler (F) comprises a fibrous substance.

9. The manufacturing method according to claim 8, wherein: The fibrous substance has a fiber length of 10 μm or more.

10. The manufacturing method according to claim 8, wherein: The fibrous material has a fiber length greater than the thickness of the electrochemical device member.

11. The manufacturing method according to claim 8, wherein: The fibrous material has a nanometer-sized fiber diameter.

12. The manufacturing method according to claim 1 or 2, wherein: The filler (F) comprises a solid lubricant selected from the following Group B, Group B: graphite, graphene, boron nitride, polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), molybdenum sulfide, tungsten disulfide, mica, talc, graphite fluoride, melamine cyanurate, and metal soap.

13. The manufacturing method according to claim 1 or 2, wherein: The filler (F) is nano-sized.

14. The manufacturing method according to claim 1 or 2, wherein: The volume fraction of the filler (F) in the molding material composition is 50 volume % or more.

15. The manufacturing method according to claim 1 or 2, wherein: The method comprises the step of irreversibly crosslinking the polymer (P1).

16. The manufacturing method according to claim 15, wherein: The cross-linking method is thermal cross-linking.

17. The manufacturing method according to claim 15, wherein: The cross-linking method is UV cross-linking.

18. The manufacturing method according to claim 15, wherein: A crosslinking agent is added to the molding material composition.

19. The manufacturing method according to claim 15, wherein: A cross-linking agent is added to the electrolyte.

20. The manufacturing method according to claim 15, wherein: The polymer (P1) is a self-crosslinking polymer.

21. The manufacturing method according to claim 1 or 2, wherein: The method includes managing the weight per unit area by measuring the thickness of the component and providing feedback.

22. The manufacturing method according to claim 1 or 2, wherein: The method comprises the step of crushing a plurality of strands formed from a molding material composition to form a sheet.

23. The manufacturing method according to claim 1 or 2, wherein: The method comprises the step of obtaining a member by chipping away from a block-shaped molding material composition.

24. The manufacturing method according to claim 1 or 2, wherein: The method includes the step of attaching the molding material composition substantially simultaneously from the front and back surfaces of the substrate.

25. The manufacturing method according to claim 1 or 2, wherein: The method comprises the steps of attaching the molding material composition to the front side of the substrate and then attaching the molding material composition to the back side.

26. The manufacturing method according to claim 1 or 2, wherein: The substrate has a conductive coating on a surface in contact with the molding material composition.

27. The manufacturing method according to claim 1 or 2, wherein: The substrate includes a polymer as a main body.

28. The manufacturing method according to claim 1 or 2, wherein: After the molding material composition is attached to the substrate, the member is not cut or perforated together with the substrate.

29. The manufacturing method according to claim 1 or 2, wherein: The component is an electrode or an insulating layer.

30. The manufacturing method according to claim 1 or 2, wherein: At least one of the shaping operations selected from group A is performed in a state where the molding material composition is not in contact with the current collector foil.

31. The manufacturing method according to claim 1 or 2, wherein: At least one of the shaping operations selected from group A is performed in a state where the molding material composition is not in contact with the porous separator.

32. The manufacturing method according to claim 1 or 2, wherein: Plasticizer (PS) is water or a mixture of water and ionic liquid. The manufacturing method includes the steps of shaping the molding material composition into a final shape when the member is arranged in a device, and then removing moisture by drying to make it a non-plasticized state.

33. The manufacturing method according to claim 32, wherein: The drying operation is performed by vacuum or heating.

34. The manufacturing method according to claim 32, wherein: The drying operation is performed in a state where the molding material composition is not in contact with the current collecting foil.

35. The manufacturing method according to claim 32, wherein: The drying operation is performed in a state where the molding material composition is not in contact with the porous separator.

36. The manufacturing method according to claim 22, wherein: The method includes the step of peeling the molding material composition adhered to a substrate from the substrate.

37. The manufacturing method according to claim 1 or 2, wherein: The method comprises the step of restoring the molding material composition or the molding material composition subjected to a cross-linking operation to a non-plasticized state by adding water or humidifying the composition again to restore the plasticized state.

38. The manufacturing method according to claim 1 or 2, wherein: The method includes the step of using scraps of the molding material composition produced in the process of shaping the molding material composition to manufacture the next component again.

39. A method for recycling a member for an electrochemical device, comprising the step of peeling off a molding material composition that has been attached to a substrate from the substrate in the manufacturing method according to any one of claims 1 to 28.

40. A method for recycling components for electrochemical devices, comprising the step of restoring the plasticized state by adding water or humidifying again after the molding material composition becomes a non-plasticized state in the manufacturing method described in any one of claims 1 to 36.

41. A method for recycling components for electrochemical devices, comprising the step of using scraps of a molding material composition produced in a process of shaping the molding material composition in the manufacturing method described in any one of claims 1 to 36 to re-manufacture a subsequent component.

42. A manufacturing method for an electrochemical device, comprising the step of obtaining a component by the method according to any one of claims 1 to 41.

43. The manufacturing method according to claim 42, wherein: The polymer (P1) is a polymer that can also be plasticized by the electrolyte solvent (ES).

44. The manufacturing method according to claim 42 or 43, wherein: The molding material composition further includes a polymer (P2) that is plasticized by the plasticizer (PS) but is insoluble in the electrolyte.

45. The manufacturing method according to claim 42 or 43, wherein: A cross-linking agent is added to the electrolyte.

46. ​​An electrochemical device member obtained by the method according to any one of claims 1 to 41. The electrochemical device member according to claim 46 , which is an electrode or an insulating layer.

48. An electrochemical device comprising the electrochemical device member according to claim 46 or 47.

49. An electrochemical device comprising an electrode obtained by the method according to any one of claims 1 to 41 and a counter electrode opposite to the electrode, the counter electrode comprising at least one selected from the group consisting of an alkali metal, an alkaline earth metal, metallic aluminum and silver.

50. The electrochemical device according to claim 48 or 49, wherein: The electrochemical device is an aqueous electrochemical device in which carrier ions are at least any one of alkali metal ions, alkaline earth metal ions, aluminum ions, silver ions, organic nitrogen cations, and halide anions.

51. The electrochemical device according to claim 48 or 49, wherein: The electrochemical device is a non-aqueous electrochemical device.

52. The electrochemical device according to claim 51, wherein The electrochemical device is a non-aqueous electrochemical device in which carrier ions are at least any one of alkali metal ions, alkaline earth metal ions, aluminum ions, silver ions, organic nitrogen cations, and halide anions.

Citation Information

Patent Citations

  • Manufacture of positive plate of nonaqueous battery

    JP1986091861A

  • Electrode paste, electrode for electrolyte cell, and their manufacture

    JP1998334886A

  • Electrolyte composition for electrochemical device and manufacturing method of electrode for electrochemical device

    JP2019114390A

  • Stacked cell and production method for same

    CN106797046A

  • Paste material for electrochemical components for batteries, fuel cells, solar cells or sensors comprises mixture of polymer matrix, electrochemically activatable inorganic liquid and optional inert powder

    DE19908532A1